Cured product, photosensitive resin composition, dry film, and printed wiring board

By using a curable resin containing amorphous silica and a specific carboxyl-containing resin on the printed wiring board, the problems of poor adhesion of mark ink and contamination of the plating solution are solved, and high recognition and good plating are achieved Effect.

CN119301201APending Publication Date: 2025-01-10TAIYO HOLDINGS CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202380043902.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-31
Filing Date
2023-03-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The marking ink of the conventional printed wiring board has poor adhesion after curing and has low discrimination, and the photosensitive resin composition is prone to contamination and poor plating during the plating solution treatment.

Method used

A specific curable resin composition contains amorphous silica and a specific proportion of carboxyl group-containing resin, and the average linear expansion rate of the cured product is controlled within the range of 70-100 ppm/°C, and the specific proportion of the photosensitive resin composition is passed. Formulated, it contains novolac type, bisphenol type and unsaturated basic acid copolymer type carboxyl-containing resin.

Benefits of technology

It improves the adhesion and visual recognition of the marking ink, suppresses contamination of the plating solution and poor plating, and meets the insulation reliability requirements of the solder resist.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160846480000411
    Figure BDA0005160846480000411
  • Figure BDA0005160846480000421
    Figure BDA0005160846480000421
  • Figure BDA0005160846480000441
    Figure BDA0005160846480000441
Patent Text Reader

Abstract

Provided is a cured product which can be easily coated with a marking ink on the surface, has excellent adhesiveness with the cured marking ink, and can form a mark having excellent visibility of characters and marks on the surface. The cured product is composed of a curable resin composition, the curable resin composition contains a curable resin and an inorganic filler, the inorganic filler contains amorphous silica, and the average linear expansion coefficient of the cured product having a thickness of 20 [mu] m is 70-100 ppm / DEG C when the temperature changes from 0 DEG C to 180 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references of related applications

[0002] This application claims priority based on Special Application No. 2022-0680840 filed in Japan on March 31, 2022 and Special Application No. 2022-060828 filed in Japan on March 31, 2022, and the contents of which are incorporated herein. Technical Field

[0003] The present invention relates to a cured product and a photosensitive resin composition, and more particularly to a cured product of a curable resin composition, a photosensitive resin composition and a dry film, and a printed wiring board having a coating composed of the cured product. Background Art

[0004] Generally speaking, in printed wiring boards used in electronic devices, in order to prevent solder from being attached to unnecessary parts of the printed wiring board during processes such as solder reflow when electronic components are mounted on the printed wiring board, a solder mask is formed in areas other than the connection holes on a substrate on which a circuit pattern is formed. The solder mask is formed by curing a liquid curable resin composition applied to a substrate, or by using a curable dry film instead of a liquid curable resin composition. As a composition suitable for forming a solder mask, for example, a curable resin composition is disclosed in Patent Document 1, which contains a carboxyl-containing resin, an acrylic copolymer, an epoxy resin, etc. having a specific acid value. In addition, Patent Document 2 discloses a photosensitive film laminate for forming a solder mask, which has a layer containing inorganic particles as a dry film.

[0005] However, on the surface of the printed wiring board, in order to know the mounting position of the electronic components to be mounted in consideration of the subsequent mounting process of the electronic components, there are cases where the information is printed with identification characters, symbols, etc. (marking) using marking ink. As marking ink, mainly used are heat-curing and UV-curing types formed by pattern printing, or alkali-developable types formed by exposing through a negative film and removing the unexposed part with an alkaline aqueous solution. In addition, a technology called laser marking has recently been used, which changes the color tone of the irradiated part by irradiating a laser to display characters, symbols, etc.

[0006] As described above, when a mark is formed by a marking ink on a printed wiring board having a solder resist layer, the marking ink may be difficult to print, easily peeled off, and the visibility of the mark may be reduced depending on the coating conditions and curing conditions of the marking ink. In particular, when the curing conditions of the marking ink are strict (for example, the marking ink is composed of a photocurable and thermosetting resin composition, and both photocuring and thermocuring are required to cure the ink), the tendency is significant.

[0007] On the other hand, the solder resist layer has various requirements such as solder heat resistance, crack resistance, insulation reliability, etc., and a photosensitive resin composition that satisfies these required characteristics is being studied. For example, in Patent Document 3, as a photosensitive resin composition that can suppress the generation of cracks without reducing heat resistance, it is proposed to use a bisphenol type carboxyl-containing resin and a novolac type carboxyl-containing resin together.

[0008] In addition, in the manufacturing process of a printed wiring board, gold plating or tin plating is usually performed for surface treatment of a conductor pattern, formation of terminals for printed contacts, formation of bonding pads, etc. after forming a solder mask. In these plating processes, since it is not necessary to energize or plate leads, electroless gold plating or electroless tin plating is performed, so it is also required to improve the plating solution resistance in the photosensitive resin composition. For example, in Patent Document 4, as a photosensitive resin composition having excellent chemical resistance such as a plating solution, it is proposed to use a bisphenol-type carboxyl-containing resin and a carboxyl-containing resin as a reactant of an unsaturated alkaline copolymer resin and an unsaturated compound containing an alicyclic epoxy group.

[0009] If the photosensitive resin composition described in Patent Document 3 is used, the plating solution is easily contaminated during electroless plating, and plating failure may occur and the frequency of replacement of the plating solution may increase. In addition, if the photosensitive resin composition described in Patent Document 4 is used, the development residue will adhere to the substrate again during the development process after exposure, and plating failure may occur due to the influence of the attached development residue.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 10-142793

[0013] Patent Document 2: Japanese Patent Application Publication No. 2018-169537

[0014] Patent Document 3: Japanese Patent Application Publication No. 2017-529551

[0015] Patent Document 4 International Application Publication No. WO2003 / 032089 Summary of the invention

[0016] Therefore, the present invention has been made in view of the above problems, and its object is to provide a cured product that can easily be coated with a marking ink on the surface, has excellent adhesion to the cured marking ink, and can form a mark with excellent visibility of characters and symbols on the surface. In addition, another object of the present invention is to provide a photosensitive resin composition that satisfies the properties required of a solder resist such as insulation reliability, can suppress contamination of a plating solution, and can also suppress plating defects.

[0017] In view of the above problems, the inventors of the present invention have conducted various studies and found that the printability and adhesion of the marking ink on the surface of the cured product affect the state of the cured coating film of the curable resin composition when the cured product is formed. That is, it was found that if the cured coating film is warped or cracks are generated on the surface during the formation of the cured product, even if the marking ink is printed later, it cannot be printed well, and even if it can be printed, it will peel off in the process after curing. Furthermore, the inventors found that in order to prevent warping or cracking, as long as the curable resin composition contains specific silica, the average linear expansion coefficient of the cured product after the curable resin composition is cured is within a specific range, and the above problems can be solved.

[0018] Furthermore, by using three specific carboxyl group-containing resins as the photosensitive resin component, a photosensitive resin composition can be obtained which satisfies the properties required of a solder resist such as insulation reliability and can suppress contamination of the plating solution and plating defects.

[0019] That is, the gist of the present invention is as follows.

[0020] [1] A cured product, which is a cured product composed of a curable resin composition, wherein the curable resin composition contains a curable resin and an inorganic filler, characterized in that:

[0021] The inorganic filler comprises amorphous silicon dioxide,

[0022] The average linear expansion coefficient of the cured product when the temperature changes from 0° C. to 180° C. is 70 to 100 ppm / ° C.

[0023] [2] The cured product according to [1], wherein the glass transition temperature (Tg) is within the range of 100 to 120°C.

[0024] [3] The cured product according to [1], wherein the average linear expansion coefficient of the cured product when the temperature changes from 0°C to 180°C is 70 to 85 ppm / °C.

[0025] [4] The cured product according to [1], wherein the curable resin includes a thermosetting resin and a photocurable resin.

[0026] [5] The cured product according to [1], wherein the amorphous silica is contained in an amount of 2 to 30% by mass based on the total amount of the curable resin composition, as converted to solid content.

[0027] [6] A photosensitive resin composition comprising (A) a carboxyl group-containing resin, (B) a photopolymerizable monomer, and (C) a thermosetting component, wherein:

[0028] (A) The carboxyl group-containing resin comprises:

[0029] (A1) a carboxyl-containing resin having a novolac skeleton;

[0030] (A2) a carboxyl group-containing resin having a bisphenol skeleton; and

[0031] (A3) unsaturated acid copolymer type carboxyl group-containing resin,

[0032] The total amount of the carboxyl-containing resin (A1) and the carboxyl-containing resin (A2) is 60 to 80% by mass based on the total amount of the carboxyl-containing resin (A).

[0033] The amount of the carboxyl group-containing resin (A3) blended is 40 to 20% by mass based on the total amount of the carboxyl group-containing resin (A).

[0034] [7] According to the photosensitive resin composition described in [6], the carboxyl group-containing resin (A3) is a reaction product of an unsaturated primary acid copolymer resin and an unsaturated compound containing an alicyclic epoxy group.

[0035] [8] The photosensitive resin composition according to [6], wherein the amount of the carboxyl group-containing resin (A1) blended is 10 to 60% by mass based on the total amount of the carboxyl group-containing resin (A).

[0036] [9] The photosensitive resin composition according to [6], wherein the amount of the carboxyl group-containing resin (A1) blended is 20 to 50% by mass based on the total amount of the carboxyl group-containing resin (A).

[0037]

[10] The photosensitive resin composition according to [6], wherein the (C) thermosetting component comprises an epoxy resin having an isocyanurate ring.

[0038]

[11] The photosensitive resin composition according to [6], further comprising (D) an inorganic filler.

[0039]

[12] The photosensitive resin composition according to

[11] , wherein the (D) inorganic filler comprises fused silica.

[0040]

[13] A dry film, wherein:

[0041] The present invention comprises a resin layer obtained by applying the photosensitive resin composition described in [6] on a first film and drying the resultant film.

[0042]

[14] A cured product, wherein:

[0043] The photosensitive resin composition described in [6] or the resin layer of the dry film described in

[13] is a cured product obtained by curing.

[0044]

[15] The cured product according to [1] or

[14] , which is used for a solder resist.

[0045]

[16] A printed wiring board comprising the cured product according to [1] or

[14] on a substrate.

[0046] According to the cured product of the present invention, the marking ink can be easily applied to the surface, the cured marking ink has excellent adhesion, and a mark with excellent visibility of characters or symbols can be formed on the surface.

[0047] According to the photosensitive resin composition of the present invention, by using three specific carboxyl group-containing resins in combination at a specific ratio, it is possible to obtain properties required of a solder resist such as insulation reliability, while suppressing contamination of a plating solution and suppressing plating defects. DETAILED DESCRIPTION

[0048] [definition]

[0049] In the present invention, the "average linear expansion coefficient" refers to a ratio indicating the expansion of the length of a cured product as a test piece by about 1°C due to a temperature rise.

[0050] In addition, the cured product in the present invention refers to a substance obtained by curing a curable resin composition, a photosensitive resin composition, and a resin layer in a dry film (hereinafter sometimes referred to as a curable resin composition, etc.). A spread sheet containing isopropyl alcohol is placed on the surface of the curable resin composition, etc. that has been cured, and a 500 g weight is placed thereon. After standing for 1 minute, there is no curable resin composition, etc. attached to the surface of the spread sheet.

[0051] [cured material]

[0052] The cured product of the present invention is obtained by curing a curable resin composition containing a curable resin and an inorganic filler, and is characterized in that the average linear expansion coefficient of the cured product in the longitudinal direction (thickness direction and perpendicular direction) when the temperature of the cured product in a film form with a thickness of 20 μm changes from 0°C to 180°C is 70 to 100 ppm / °C. According to the present invention, if the cured product has an average linear expansion coefficient within the above range, it is easy to apply a marking ink on the surface, and the adhesion with the cured marking ink is excellent, and further, a mark with excellent visibility of text or marks can be formed on the surface. The reason is uncertain, but it can be inferred as follows. That is, if the cured product has an average linear expansion coefficient of 70 to 100 ppm / °C when the temperature is increased from 0°C to 180°C, it is not easy to warp or crack on the surface when the curable resin composition is cured to form a cured product. As a result, it is considered that a marking ink can be applied to the surface of the cured product to form a mark with high visibility. In addition, the curable resin composition contains amorphous silica as an inorganic filler. The surface smoothness of the amorphous silica is lower than that of other silicas. Therefore, due to its anchoring effect, the adhesion between the cured product and the marking ink is also improved, so that the marking material can be prevented from peeling off from the surface of the cured product. The more preferred average linear expansion coefficient is 70 to 85 ppm / °C.

[0053] The average linear expansion coefficient of the cured product can be measured by a conventional method using a thermomechanical analyzer, but in the present invention, it refers to a value measured as follows.

[0054] First, a curable resin composition was applied onto a copper foil, dried, and then heated and irradiated with light to obtain a flat film-like cured product having a thickness of 20 μm after curing.

[0055] Next, the obtained cured product was cut into test pieces with a width of 3 mm and a length of 30 mm, and the thermal expansion coefficient was measured in the tensile mode using a thermomechanical analyzer (TMA / SS6000, manufactured by Seiko Instruments). The maximum tensile load is 50 N / m, the span (distance between chucks) is 10 mm, and the heating rate is 10°C / min. The test piece was mounted on the thermomechanical analyzer, heated from 30°C to 200°C, and left for 10 minutes. Then, it was cooled to -30°C at a cooling rate of -10°C / min, and measured at a heating rate of 10°C / min from -30°C to 250°C. The measured values ​​at 0°C and 180°C were read, and the average linear expansion coefficient (α) was calculated by the following formula.

[0056] α=(1 / LS)×[{L(180)-L(0)} / (T(180)-T(0)]

[0057] (In addition,

[0058] LS: Length of the test piece (cured product) before measurement (measured value)

[0059] L(0): Change in length of the test piece (cured product) at 0°C (measured value)

[0060] L(180): Change in length of the test piece (cured product) at 180°C (measured value)

[0061] T(0): 0(℃)

[0062] T(180): 180(℃).

[0063] In addition, the cured product of the present invention preferably has a glass transition temperature (Tg) in the range of 100 to 120°C. By having a cured product with Tg within this range, the linear expansion coefficient is also easily within the desired range, resulting in a stable cured product and improved labeling adhesion. In addition, the Tg of the cured product of the present invention can be determined by the following content using a TMA curve measured by a thermomechanical analyzer (TMA). That is, a straight line A passing through the two points of 0°C and 30°C and a straight line B passing through the two points of 150°C and 180°C are respectively derived from the TMA curve when measured under the same conditions as the average linear expansion coefficient, and the temperature of the point (extrapolated point) where the straight line A and the straight line B intersect is used as the Tg of the cured product of the present invention.

[0064] The average linear expansion coefficient (α) of the cured product of the present invention can be appropriately adjusted according to the mixing ratio of the curable resin and the inorganic filler, the degree of actual curing by heating or light irradiation, in addition to the above-mentioned glass transition temperature. In addition, the glass transition temperature of the cured product of the present invention can be appropriately adjusted by the combination (compatibility) of the curable resin or other resins contained in the curable resin composition.

[0065] [Curable resin composition]

[0066] The cured product of the present invention is formed by curing a curable resin composition. The curable resin composition comprises a curable resin and an inorganic filler. Of course, in addition to the curable resin and the inorganic filler, it may also contain any additives such as a curing agent, a curing accelerator, and even a coloring agent for curing the curable component as required. The following describes the various components constituting the curable resin composition.

[0067] <Curing Resin>

[0068] Examples of curable resins include photocurable or thermosetting resins such as acrylic resins, epoxy resins, epoxy acrylate resins, silicone resins, phenolic resins, polyimide resins, polyurethane resins, melamine resins, and urea-formaldehyde resins having photocurable or thermosetting functional groups. These resins may be used alone or in combination of two or more. It is preferred to use any of the photocurable resins and thermosetting resins in combination, since they can exhibit excellent adhesion even under strict curing conditions such as dual curing.

[0069] As the photocurable resin, there can be listed: polymerizable monomers or oligomers. As the polymerizable monomer, it is preferable to use a photopolymerizable monomer having an ethylenically unsaturated double bond. As the photopolymerizable monomer, for example, there can be listed: well-known and commonly used polyester (meth) acrylates, polyether (meth) acrylates, urethane (meth) acrylates, carbonate (meth) acrylates, epoxy (meth) acrylates, etc. Specifically, there can be cited: hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate; diacrylates of glycols such as ethylene glycol, methoxytetraglycol, polyethylene glycol, and propylene glycol; acrylamides such as N,N-dimethylacrylamide, N-hydroxymethylacrylamide, and N,N-dimethylaminopropylacrylamide; aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; polyhydric alcohols such as hexanediol, trimethylolpropane, pentaerythritol, dipentaerythritol, tri-hydroxyethyl isocyanurate, or their ethoxylated adducts, propylene oxide adducts, or ε-caprolactone adducts, etc. Phenoxy acrylate, bisphenol A diacrylate, and polyacrylates such as ethylene oxide adducts or propylene oxide adducts of these phenols; polyacrylates of glycidyl ethers such as glycidyl diglycidyl ether, glycidyl triglycidyl ether, trimethylolpropane triglycidyl ether, and isocyanuric acid triglycidyl ether; not limited to the above, acrylates obtained by direct acrylate esterification of polyols such as polyether polyols, polycarbonate diols, hydroxyl-terminated polybutadiene, polyester polyols, or urethane acrylate esterification with diisocyanates and melamine acrylates, and at least one of the methacrylates corresponding to the above acrylates can be appropriately selected and used. Such photopolymerizable monomers can also be used as reactive diluents.

[0070] In addition, examples of polymerizable oligomers include unsaturated polyester oligomers, (meth)acrylate oligomers, etc. Examples of (meth)acrylate oligomers include epoxy (meth)acrylates such as phenol novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, and bisphenol epoxy (meth)acrylate, urethane (meth)acrylate, epoxyurethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, and polybutadiene-modified (meth)acrylate.

[0071] When the curable resin composition contains a carboxyl group-containing resin described below, the amount of the photocurable resin in the curable resin composition is preferably 1 to 40 parts by mass, more preferably 5 to 35 parts by mass, based on solid content per 100 parts by mass of the carboxyl group-containing resin.

[0072] In addition, the curable resin contained in the curable resin composition may also contain a photosensitive resin that can form a pattern by exposure and development. Such a photosensitive resin is patterned by exposure and development, and is preferred from the point of view of being able to form a resin cured film of a desired pattern on a substrate.

[0073] As the thermosetting resin of curable resin, any known one can be used.For example, amino resins such as melamine resin, benzoguanamine resin, melamine derivatives, benzoguanamine derivatives, isocyanate compounds, blocked isocyanate compounds, cyclic carbonate compounds, epoxy compounds, oxetane compounds, episulfide resins, bismaleimide, carbodiimide resins and other known compounds can be used.Particularly preferably, compounds having multiple cyclic ether groups or cyclic thioether groups (hereinafter referred to as cyclic (thio) ether groups) in the molecule are used.These thermosetting resins can be used alone as one, or two or more combinations can be used.By containing a thermosetting resin, the strength of the cured film in the subsequent process can be improved.

[0074] The compound having a plurality of cyclic (thio)ether groups in the above-mentioned molecule is a compound having a plurality of 3-, 4- or 5-membered cyclic (thio)ether groups in the molecule, and examples thereof include compounds having a plurality of epoxy groups in the molecule, i.e., polyfunctional epoxy compounds, compounds having a plurality of oxetane groups in the molecule, i.e., polyfunctional oxetane compounds, compounds having a plurality of thioether groups in the molecule, i.e., epithioether resins, and the like.

[0075] Examples of such polyfunctional epoxy compounds include bisphenol A type epoxy resins, bisphenol F type epoxy resins, hydrogenated bisphenol A type epoxy resins, brominated bisphenol A type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, biphenyl type epoxy resins, naphthalene type epoxy resins, dicyclopentadiene type epoxy resins, triphenylmethane type epoxy resins, and the like.

[0076] Examples of commercially available multifunctional epoxy compounds include jER828, 806, 807, YX8000, YX8034, and 834 manufactured by Mitsubishi Chemical Corporation, YD-128, YDF-170, ZX-1059, and ST-3000 manufactured by Nippon Steel Chemical & Materials Co., Ltd., EPICLON830, 835, 840, 850, N-730A, and N-695 manufactured by DIC Corporation, and RE-306 manufactured by Nippon Kayaku Co., Ltd.

[0077] Examples of the polyfunctional oxetane compound include bis[(3-methyl-3-oxetanylmethoxy)methyl]ether, bis[(3-ethyl-3-oxetanylmethoxy)methyl]ether, 1,4-bis[(3-methyl-3-oxetanylmethoxy)methyl]benzene, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, (3-methyl-3-oxetanyl)methacrylate, (3-ethyl-3-oxetanyl)methylmethacrylate, (3-ethyl-3-oxetanyl)methylmethacrylate or oligomers or copolymers thereof, and polyfunctional oxetanes such as oxetane alcohol and novolac resin, poly(p-hydroxystyrene), card-type bisphenols, calixarene, calixarene sol octenes, or etherified products with resins having hydroxyl groups such as silsesquioxane. In addition, copolymers of an unsaturated monomer having an oxetane ring and an alkyl (meth)acrylate, and the like are also mentioned.

[0078] Examples of compounds having a plurality of cyclic sulfide groups in the molecule include bisphenol A type episulfide resins, etc. In addition, episulfide resins, etc., in which the oxygen atoms of epoxy groups of novolac type epoxy resins are replaced with sulfur atoms, can also be prepared by the same synthesis method.

[0079] Regarding the compounding amount of the compound having multiple cyclic (sulfide) ether groups in the molecule, in the case of a carboxyl-containing resin, the number of functional groups of the compound having multiple cyclic (sulfide) ether groups in the molecule of the reaction is preferably 0.8 to 2.5 mol, more preferably 1.0 to 2.0 mol, relative to every 1.0 mol of carboxyl groups in the resin. By setting it to 0.8 mol or more, the residual carboxyl groups in the cured film can be prevented, and good heat resistance, alkali resistance, electrical insulation, etc. can be obtained. In addition, by making the above-mentioned compounding amount less than 2.5 mol, low molecular weight cyclic (sulfide) ether groups can be prevented from remaining on the dried coating film, so that the strength of the cured film can be well ensured.

[0080] The compound having a plurality of cyclic (thio)ether groups in the molecule is a polyfunctional epoxy compound. When a carboxyl group-containing resin is contained, the amount of the polyfunctional epoxy compound is preferably 20 to 50 parts by mass based on solid content per 100 parts by mass of the carboxyl group-containing resin.

[0081] Examples of amino resins such as melamine derivatives and benzoguanamine derivatives include methylolmelamine compounds, methylolbenzoguanamine compounds, methylolglycourea compounds, and methylolurea compounds.

[0082] As the isocyanate compound, a polyisocyanate compound may be mixed. Examples of the polyisocyanate compound include aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, naphthalene-1,5-diisocyanate, o-xylene diisocyanate, m-xylene diisocyanate, and 2,4-trimethylene; aliphatic polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, methylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4-methylenebis(cyclohexyl isocyanate), and isophorone diisocyanate; alicyclic polyisocyanates such as dicycloheptane triisocyanate; and adducts, biuret bodies, and isocyanurate bodies of the above isocyanate compounds.

[0083] As the blocked isocyanate compound, a polyaddition reaction product of an isocyanate compound and an isocyanate blocking agent can be used. As the isocyanate compound that can react with the isocyanate blocking agent, for example, the above-mentioned polyisocyanate compounds can be listed. As the isocyanate blocking agent, for example, phenol blocking agents; lactam blocking agents; active methylene blocking agents; alcohol retarders; oxime retarders; thiol blocking agents; amide blocking agents; imide blocking agents; amine blocking agents; imidazole blocking agents; imine blocking agents, etc. can be listed.

[0084] In the present invention, the curable resin is preferably an alkali-soluble resin from the viewpoint of being developable during patterning. When the curable resin composition contains an alkali-soluble resin, it is preferred to contain a photopolymerizable monomer or a photopolymerization initiator as other components.

[0085] As long as the alkali-soluble resin is a resin that dissolves in an alkaline aqueous solution, known and commonly used resins can be used. Alkali-soluble resins can be used alone or in combination of two or more. As examples, water-soluble resins such as carboxyl-containing resins and phenolic hydroxyl-containing resins can be cited. Among them, from the viewpoint of excellent developability, carboxyl-containing resins and phenolic hydroxyl-containing resins are preferred, and carboxyl-containing resins are more preferred. Carboxyl-containing resins can form alkali developability by containing carboxyl groups. In addition, from the viewpoint of photosensitivity, in addition to carboxyl groups, it is preferred that the molecule has ethylenically unsaturated double bonds, but only carboxyl-containing resins without ethylenically unsaturated double bonds can also be used. Ethylenically unsaturated double bonds are preferably derived from acrylic acid or methacrylic acid or their derivatives. In the case of using only carboxyl-containing resins without ethylenically unsaturated double bonds, in order to make the composition photocurable, it is necessary to use a compound having multiple ethylenically unsaturated groups in the molecule, i.e., a photopolymerizable monomer. As specific examples of carboxyl-containing resins, the following compounds (any one of oligomers and polymers) can be cited. In the present specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate, and a mixture thereof, and the same applies to other similar expressions.

[0086] (1) Carboxyl group-containing resins obtained by copolymerizing unsaturated carboxylic acids such as (meth)acrylic acid with unsaturated group-containing compounds such as styrene, α-methylstyrene, (meth)acrylic acid lower alkyl esters, isobutylene, etc.

[0087] (2) Carboxyl resins produced by the addition polymerization of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, and diol compounds containing carboxyl groups such as dimethylol propionic acid and dimethylol butyric acid, as well as diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A-based oxyalkylene adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.

[0088] (3) Carboxyl-containing photosensitive polyurethane resins produced by the polyaddition reaction of partially anhydride-modified products of difunctional epoxy resins such as diisocyanates, bisphenol A epoxy resins, hydrogenated bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, dioxane epoxy resins, and bisphenol epoxy resins with monocarboxylic acid compounds having ethylenically unsaturated double bonds such as (meth)acrylic acid, and carboxyl-containing dioxane compounds and diol compounds.

[0089] (4) In the synthesis of the resin of (2) or (3) above, a compound having one hydroxyl group and one or more (meth)acryloyl groups is added to the molecule of a hydroxyalkyl (meth)acrylate to prepare a carboxyl group-containing photosensitive polyurethane resin which is terminally (meth)acrylated.

[0090] (5) In the synthesis of the resin of (2) or (3), a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule, such as isophorone diisocyanate and pentaerythritol triacrylate in an equimolar ratio, is added, and a carboxyl-containing photosensitive polyurethane resin is terminally (meth)acryloylated.

[0091] (6) A carboxyl group-containing photosensitive resin obtained by reacting (meth)acrylic acid with a difunctional or higher polyfunctional (solid) epoxy resin to add a dibasic acid anhydride to a hydroxyl group present in a side chain.

[0092] (7) A carboxyl group-containing photosensitive resin obtained by reacting (meth)acrylic acid with a polyfunctional epoxy resin obtained by epoxidizing the hydroxyl groups of a bifunctional (solid) epoxy resin with epichlorohydrin, and adding a dibasic acid anhydride to the generated hydroxyl groups.

[0093] (8) A carboxyl-containing polyester resin obtained by reacting a dicarboxylic acid such as adipic acid, phthalic acid, or hexahydrophthalic acid with a difunctional oxetane resin and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the generated primary hydroxyl group.

[0094] (9) A carboxyl group-containing photosensitive resin obtained by reacting a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule of an epoxy compound having multiple epoxy groups in one molecule, such as p-hydroxyphenylene glycol, with a monocarboxylic acid containing an unsaturated group such as (meth)acrylic acid, and reacting a polyacid anhydride such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, adipic acid, etc. with the alcoholic hydroxyl group of the obtained reaction product.

[0095] (10) A carboxyl group-containing photosensitive resin obtained by reacting a compound having a plurality of phenolic hydroxyl groups in one molecule with an alkylene oxide such as ethylene oxide or propylene oxide to obtain a reaction product with an unsaturated group-containing monocarboxylic acid and then reacting a polybasic acid anhydride with the reaction product.

[0096] (11) A carboxyl group-containing photosensitive resin obtained by reacting a reaction product obtained by reacting a compound having a plurality of phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, a reaction product obtained by reacting a monocarboxylic acid containing an unsaturated group, and a polybasic acid anhydride.

[0097] (12) A carboxyl group-containing photosensitive resin obtained by adding a compound having one epoxy group and one or more (meth)acryloyl groups in one molecule to the resins of (1) to (11).

[0098] In the present specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate, and a mixture thereof, and the same applies to other similar expressions.

[0099] Among the above-mentioned carboxyl-containing photosensitive resins, it is preferred to use a novolac type epoxy resin as the epoxy resin in the photosensitive resin (6), a bisphenol type epoxy resin as the epoxy resin in the photosensitive resin (7), and a photosensitive resin (12). In particular, it is more preferred to use at least two of the above-mentioned (6), (7), and (12), and it is further preferred to use three of them.

[0100] The (6) is preferably contained in a ratio of 10 to 80% by mass, more preferably 10 to 60% by mass, and even more preferably 10 to 40% by mass, based on the entire carboxyl group-containing resin.

[0101] The (7) is preferably contained in a ratio of 20 to 70% by mass, more preferably 30 to 60% by mass, and even more preferably 40 to 55% by mass, based on the entire carboxyl group-containing resin.

[0102] The (12) is preferably contained in a ratio of 20 to 40% by mass, more preferably 25 to 40% by mass, based on the entire carboxyl group-containing resin.

[0103] These carboxyl group-containing resins are not limited to the resins listed above, and may be used alone or in combination of two or more.

[0104] The acid value of the carboxyl-containing resin is preferably 40 to 150 mgKOH / g. By making the acid value of the carboxyl-containing resin 40 mgKOH / g or more, alkali development becomes good. In addition, by making the acid value 150 mgKOH / g or less, a good resist pattern can be easily drawn. More preferably, it is 50 to 130 mgKOH / g.

[0105] The weight average molecular weight of the carboxyl-containing resin varies depending on the resin skeleton, but is generally preferably 2,000 to 150,000. By making the weight average molecular weight 2,000 or more, wrinkle-free performance and resolution can be improved. In addition, by making the weight average molecular weight 150,000 or less, developability and storage stability can be improved. More preferably, it is 5,000 to 30,000. In addition, the weight average molecular weight can be measured by gel permeation chromatography (GPC).

[0106] In the curable resin composition, the compounding amount of the carboxyl group-containing resin is preferably 20 to 60% by mass based on the solid content. By setting it to 20% by mass or more, the coating strength can be improved. In addition, by setting it to 60% by mass or less, the viscosity becomes appropriate and the printability is improved. More preferably, it is 25 to 50% by mass.

[0107] From the viewpoint of printability or adhesiveness of the marking ink, the total amount of the curable resin in the curable resin composition is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, based on the total curable resin composition in terms of solid content.

[0108] When the curable resin composition for forming the cured product of the present invention contains a carboxyl group-containing resin, a photopolymerizable monomer, or an oligomer, it may contain a photopolymerization initiator for reacting them by exposure. As the photopolymerization initiator, any known photopolymerization initiator may be used.

[0109] Examples of the photopolymerization initiator include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and the like; 2,6-dimethoxybenzoyl Monoacylphosphine oxides such as 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphine oxide, methyl 2,4,6-trimethylbenzoylphenylphosphine oxide, isopropyl pivaloylphenylphosphine, 2,4,6-trimethylbenzoyldiphenylphosphine oxide; ethyl phenyl (2,4,6-trimethylbenzoyl)phosphine, 1-hydroxy-cyclohexylphenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl]-2-methyl-1-propane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, etc. Hydroxyacetophenones; benzoins such as benzoin, benzyl, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, benzoin n-butyl ether; benzoin alkyl ethers; benzophenones such as benzophenone, p-methyl benzophenone, michelsone, methyl benzophenone, 4,4'-dichlorobenzophenone, 4,4'-diethylaminobenzophenone; acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)-butanone-1,2-(dimethyl Acetophenones such as 2-[(4-methylphenyl)methyl)-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone, etc.; thioxanthones such as 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, 2,4-diisopropylthioxanthone, etc.; anthraquinones such as anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, 2-aminoanthraquinone, etc.; ketals such as acetophenone dimethyl ketal, benzyl dimethyl ketal, etc.; benzoic acid esters such as ethyl-4-dimethylaminobenzoate, 2-(dimethylamino)ethyl benzoate, and ethyl p-dimethylbenzoate;1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxy)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetoximate) and other oxime esters; bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1-propyl-1-yl)ethyl)phenyl]titanium and other titanium olefins; phenyl disulfide 2-nitrofluorene, butyne, anisole, azobisisobutyronitrile, tetramethylthiuram disulfide, etc. These photopolymerization initiators can be used alone or in combination of two or more. ;

[0110] Commercially available products of α-aminoacetophenone-based photopolymerization initiators include Omnirad 907, 369, 369E, and 379 manufactured by Agenmon Resins. Commercially available products of acylphosphine oxide-based photopolymerization initiators include Omnirad 819 manufactured by Agenmon Resins. Commercially available products of oxime ester-based photopolymerization initiators include Irgacure OXE01 and OXE02 manufactured by BASF Japan Co., Ltd., N-1919 manufactured by ADEKA ARKLS NCI-831 and NCI-831E, and TR-PBG-304 manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.

[0111] In addition, carbazole oxime ester compounds described in JP-A-2004-359639, JP-A-2005-097141, JP-A-2005-220097, JP-A-2006-160634, JP-A-2008-094770, JP-T-2008-509967, JP-T-2009-040762, and JP-A-2011-80036 can be cited.

[0112] When the curable resin composition contains a carboxyl group-containing resin, the amount of the photopolymerization initiator is preferably 1 to 30 parts by mass relative to 100 parts by mass of the carboxyl group-containing resin, calculated as solid content. When the amount is 1 part by mass or more, the curable resin composition has good photocurability and good coating properties such as chemical resistance. In addition, when the amount is 30 parts by mass or less, the effect of reducing exhaust gas can be obtained, and the light absorption on the surface of the cured coating is good, and the deep curability is difficult to reduce. More preferably, it is 2 to 25 parts by mass.

[0113] In addition, in the present invention, a photoinitiator auxiliary agent or a sensitizer may be used together with the photopolymerization initiator. As the photoinitiator auxiliary agent or the sensitizer, there may be listed: benzoin compounds, anthraquinone compounds, thioxanthone compounds, ketal compounds, benzophenone compounds, tertiary amine compounds, and xanthone compounds. It is particularly preferred to use thioxanthone compounds such as 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, 2-isopropylthioxanthone, and 4-isopropylthioxanthone. By containing thioxanthone compounds, the deep curing property can be improved. These compounds can sometimes be used as photopolymerization initiators, but are preferably used together with the photopolymerization initiator. In addition, the photoinitiator auxiliary agent or the sensitizer may be used alone or in combination of two or more.

[0114] These photopolymerization initiators, photoinitiator aids and sensitizers sometimes reduce sensitivity due to absorption of specific wavelengths, and sometimes function as ultraviolet absorbers. However, they are not only used to improve the sensitivity of curable resin compositions. They can also absorb light of specific wavelengths as needed to improve the photoreactivity of the surface, change the line shape and opening of the resist pattern to vertical, conical, or inverted conical, and improve the accuracy of the line width and opening diameter.

[0115] In addition, when the curable resin composition for forming the cured product of the present invention contains a thermosetting resin, it may also contain a thermosetting catalyst for accelerating its curing. Examples of the thermosetting catalyst include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N, N-dimethylbenzylamine, 4-methoxy-N, N-dimethylbenzylamine, 4-methyl-N, N-dimethylbenzylamine, hydrazine compounds such as adipic acid dihydrazide, sebacic acid dihydrazide, and phosphorus compounds such as triphenylphosphine. In addition, commercially available products include, for example, 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, 2P4MHZ (all trade names of imidazole compounds) manufactured by Shikoku Chemicals Co., Ltd., U-CAT3513N (a trade name of a dimethylamine compound) manufactured by San Apro Co., Ltd., DBU, DBN, U-CATSA102 (all bicyclic amidine compounds and their salts), etc.

[0116] The compounds are not limited to the above compounds. As long as they are compounds that serve as heat curing catalysts for epoxy resins or oxetane compounds, or compounds that promote the reaction of at least one of epoxy and oxetane groups with carboxyl groups, they can be used alone or in combination of two or more. In addition, guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-S-triazine, 2-vinyl-2,4-diamino-S-triazine, 2-vinyl-4,6-diamino-S-triazine isocyanuric acid adducts, 2,4-diamino-6-methacryloyloxyethyl-S-triazine isocyanuric acid adducts and other S-triazine derivatives can also be used. It is preferred that these compounds used as adhesion promoters be used together with a heat curing catalyst.

[0117] The above-mentioned heat-curing catalyst can be used alone or in combination of two or more. From the viewpoint of the storage stability of the photosensitive resin composition and the heat resistance of the cured film, when the curable resin composition contains a carboxyl group-containing resin, the mixing amount of the heat-curing catalyst is preferably 0.01 to 8 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the carboxyl group-containing resin, based on solid content conversion.

[0118] <Inorganic filler>

[0119] The cured product of the present invention is formed by curing a curable resin composition containing amorphous silica as an inorganic filler. By containing amorphous silica, the printability when printing marking ink on the surface of the cured product, the adhesion of the printed mark and its visibility are greatly improved. The reason is unclear, but it is considered as follows. That is, since the surface smoothness of amorphous silica is lower than that of crystalline silica, it can be considered that the printability and adhesion are improved by its anchoring effect. In addition, amorphous silica in the present invention refers to silica other than crystalline silica (crystalline silica also includes fine silica), which does not have long-range order like crystalline silica, but has a short-range ordered material state. This is a non-equilibrium metastable state in thermodynamics. Amorphous silica can use well-known and commonly used silica, and can be listed as: silica gel, diatomaceous earth, etc. In addition, amorphous silica can also be synthetic silica as long as it is amorphous.

[0120] From the viewpoint of the coating property of the marking ink and the adhesion to the marking ink during curing, the oil absorption of the amorphous silica is preferably 180 to 350 ml / 100 g. Such amorphous silica is porous, and through the absorption of oil by organic solvents during curing or drying, the amorphous silica or other body pigments become denser, as a result of which it can be inferred that the coating property or adhesion of the marking ink is improved. The oil absorption is more preferably 200 to 300 ml / 100 g. In addition, in the present invention, the oil absorption refers to the oil absorption measured according to "JIS K5101-13-1:2004 Pigment Test Methods - Part 13: Oil Absorption - Section 1: Refined Linseed Oil Method".

[0121] Amorphous silica can use known and commonly used silica, which can be synthetic or natural. In addition, it can be surface treated or not. The type of surface treatment is the same as that of the extender pigment. As products, ACEMATT 82, ACEMATT 790, ACEMATT OK 412, ACEMATT OK 500 (all manufactured by Evonik Degussa) and the like can be listed.

[0122] The above-mentioned amorphous silica may also be silica that has been surface treated in order to improve dispersibility in the curable resin composition. By using amorphous silica that has been surface treated, aggregation can be suppressed. The surface treatment method is not particularly limited, and a known and conventional method can be used, but it is preferred to treat the surface of the amorphous silica using a surface treatment agent having a curable reactive group, such as a coupling agent having a curable reactive group as an organic group.

[0123] As coupling agents, coupling agents such as silanes, titanates, aluminates and zirconium aluminates can be used. Among them, silane coupling agents are preferred. As examples of the silane coupling agents involved, vinyl trimethoxysilane, vinyl triethoxysilane, N-(2-aminomethyl)-3-aminopropyl methyl dimethoxysilane, N-(2-aminoethyl)-3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-anilinopropyl trimethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methoxypropyl trimethoxysilane, etc. can be listed. They can be used alone or together. These silane coupling agents are preferably fixed on the surface of the filler by adsorption or reaction in advance.

[0124] The average particle size (D50) of amorphous silica may preferably be 0.1 to 10 μm, more preferably 1 to 5 μm. In addition, the average particle size refers to the particle size of 50% of the volume cumulative obtained using a laser diffraction scattering particle size distribution measurement method. In addition, the average particle size of amorphous silica refers to the value measured as described above for silica before modulating (pre-stirring, kneading) the curable resin composition.

[0125] From the viewpoint of printability and adhesiveness of the marking ink, the amount of amorphous silica compounded in the curable resin composition is preferably 2 to 30% by mass, more preferably 5 to 20% by mass, based on the total amount of the curable resin composition, in terms of solid content.

[0126] In the curable resin composition, in addition to the above-mentioned amorphous silica, in order to improve the physical strength of the cured product, other inorganic fillers can be mixed as needed. As an inorganic filler, known substances can be used, and in particular, talc, mica, aluminum oxide, calcium oxide, magnesium oxide, zinc oxide, calcium carbonate, magnesium carbonate, fly ash, dewatered sludge, kaolin, clay, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, hydrotalcite, aluminum silicate, magnesium silicate, calcium silicate, wollastonite, potassium titanate, magnesium sulfate, calcium sulfate, magnesium phosphate, sepiolite, boron nitride, boron nitride, silicon dioxide balloon, glass balloon, ironmaking slag, copper, ferrite, etc., magnetic powder, cement, glass powder, Neuburg silica, antimony trioxide, magnesium oxide, hydrated aluminum, hydrated gypsum, alum and barium sulfate, etc. Other inorganic fillers can be used alone or in combination of two or more.

[0127] The average particle size (D50) of the inorganic filler is preferably 0.1 to 200 μm, more preferably 1 to 10 μm, from the viewpoint of dispersibility, etc. Also, the inorganic filler may be surface treated from the viewpoint of dispersibility, similarly to amorphous silica.

[0128] The total amount of the inorganic filler mixed with the amorphous silica is preferably 20 to 70% by mass, more preferably 40 to 60% by mass, relative to the total curable resin composition, based on solid content. Thus, the anti-adhesive force reduction and thermal cycle resistance of the curable resin composition are improved, and as a result, the adhesion to the marking ink can be further improved.

[0129] <Other ingredients>

[0130] The curable resin composition of the present invention may be mixed with, in addition to the above-mentioned components, colorants, elastomers, mercapto compounds, urethanization catalysts, thixotropic agents, adhesion promoters, block copolymers, chain transfer agents, polymerization inhibitors, copper damage inhibitors, antioxidants, rust inhibitors, thickeners such as organic bentonite and montmorillonite, at least one of silicone, fluorine, and polymer defoamers and leveling agents, and flame retardants such as phosphate compounds such as phosphonates, phosphate ester derivatives, and phosphazene compounds, etc., as needed. These may be those known in the field of electronic materials.

[0131] In the curable resin composition, an organic solvent may be mixed from the viewpoint of ease of preparation and coating properties. As the organic solvent, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; petroleum ether, petroleum naphtha, solvent naphtha, and other petroleum solvents such as well-known and commonly used organic solvents. These organic solvents may be used alone or in combination of two or more.

[0132] The amount of the organic solvent blended in the curable resin composition can be appropriately changed according to the materials constituting the curable resin composition. For example, when the curable resin composition contains a carboxyl group-containing resin, the amount can be 20 to 300 parts by mass relative to 100 parts by mass of the carboxyl group-containing resin (solid content).

[0133] The curable resin composition may be used in a dry film form or in a liquid form. When used in a liquid form, it may be a one-component or two-component or more liquid form.

[0134] [Photosensitive resin composition]

[0135] The photosensitive resin composition of the present invention contains (A) a carboxyl group-containing resin, (B) a photopolymerizable monomer, and (C) a thermosetting component as essential components. Hereinafter, each component constituting the photosensitive resin composition of the present invention will be described.

[0136] <(A) Carboxyl-containing resin>

[0137] The photosensitive resin composition of the present invention contains three carboxyl-containing resins (A1) having a novolac skeleton, (A2) having a bisphenol skeleton, and (A3) being a copolymer of unsaturated primary acids as carboxyl-containing resins in specific ratios. In the present invention, by containing the above three specific photosensitive resins in specific ratios as carboxyl-containing resins, a photosensitive resin composition can be obtained that satisfies the properties required by solder resists such as heat resistance and insulation reliability, and can suppress contamination of the plating solution and poor plating. The reason is uncertain, but it can be inferred as follows.

[0138] As described in the above-mentioned patent document 4, as a photosensitive resin, when a carboxyl-containing resin having a bisphenol skeleton and a carboxyl-containing resin of an unsaturated primary acid copolymer type are used together, the insulation reliability and heat resistance of PCBT are excellent due to the high hydrophobicity and large molecular weight of the resin. On the other hand, the copolymer resin component in the uncured resin component dissolved in the developer is precipitated into the water tank in the cleaning process after the development treatment, and is attached to the conductor part (copper) of the substrate again. This attachment is considered to be the cause of poor plating in the subsequent plating treatment. On the other hand, as a photosensitive resin, when a photosensitive resin (a carboxyl-containing resin having a bisphenol skeleton or a phenolic varnish skeleton) with excellent heat resistance and crack resistance described in patent document 3 is used, although the above-mentioned development residue is hardly precipitated into the water tank, the uncured resin component or unreacted photopolymerizable monomer contained in the cured film of the photosensitive resin composition is dissolved into the non-electrolytic plating bath, contaminating the plating bath. Therefore, by using the above-mentioned three carboxyl-containing resins together in a specific ratio, the overall hydrophobicity of the photosensitive resin (inhibiting precipitation into the water tank) and the inhibition of dissolution into the plating bath can coexist in a high dimension. As a result, it can be considered that both the properties required by the solder resist such as heat resistance and insulation reliability are satisfied and the occurrence of poor plating and contamination of the plating solution can be suppressed.

[0139] Examples of the carboxyl-containing resin having a novolac skeleton (A1) include: a carboxyl-containing photosensitive resin (A1a) obtained by reacting a polyfunctional epoxy resin such as a phenol novolac epoxy resin, a cresol novolac epoxy resin, a bisphenol A cresol novolac epoxy resin, a dicyclopentadiene chloramine novolac epoxy resin, with (meth)acrylic acid, and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, etc. to the hydroxyl groups present in the side chains; and reacting the polyfunctional epoxy resin obtained by further epoxidizing the hydroxyl groups of the polyfunctional epoxy resin with epichlorohydrin with (meth)acrylic acid to produce a polyfunctional epoxy resin. A carboxyl-containing photosensitive resin (A1b) obtained by adding a polybasic acid anhydride to a hydroxyl group of a phenolic resin, a carboxyl-containing photosensitive resin (A1c) obtained by adding a cyclic ether such as ethylene oxide or a cyclic carbonate such as propylene carbonate to a polyfunctional phenol compound such as a novolac resin, partially esterifying the obtained hydroxyl group with (meth) acrylic acid, and reacting the polybasic acid anhydride with the remaining hydroxyl group, and further adding a carboxyl-containing photosensitive resin containing one epoxy group and one or more (meth)acryloyl groups in the molecule such as (meth) acrylate glycidyl ester and (meth) acrylate α-methyl glycidyl ester to any of the above-mentioned resins A1a to A1c. In the present invention, the solder heat resistance of the cresol novolac type carboxyl-containing resin is superior to that of the phenol novolac type carboxyl-containing resin, and therefore it is preferred. In addition, in this specification, "(meth) acrylate" refers to the general term for acrylates, methacrylates and mixtures thereof, and the same applies to other similar expressions. In addition, the term "(meth)acryloyl" is used as a term collectively referring to acryloyl, methacryloyl, and both of them, and the same applies to other similar expressions.

[0140] Examples of the carboxyl-containing resin (A2) having a bisphenol skeleton include: a carboxyl-containing photosensitive resin (A2a) obtained by reacting a difunctional epoxy resin such as bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, or bisphenol S epoxy resin with (meth)acrylic acid, and adding a polybasic acid anhydride to the generated hydroxyl groups; a carboxyl-containing photosensitive resin (A2b) obtained by reacting a polyfunctional epoxy resin obtained by further epoxidizing the hydroxyl groups of the above-mentioned difunctional epoxy resin with (meth)acrylic acid, and adding a polybasic acid anhydride to the generated hydroxyl groups; and a carboxyl-containing photosensitive resin obtained by further adding a compound having one epoxy group and one or more (meth)acryloyl groups in the molecule such as glycidyl (meth)acrylate or α-methylglycidyl (meth)acrylate to the above-mentioned resin A2a or A2b.

[0141] Each of the carboxyl-containing resins (A1) and (A2) described above has a plurality of free carboxyl groups on the side chains of the backbone polymer, and therefore can be developed using an alkaline aqueous solution. The acid value of the carboxyl-containing resins (A1) and (A2) is preferably 40 to 200 mgKOH / g. If the acid value of the carboxyl-containing resins of A1 and A2 is 40 to 200 mgKOH / g, alkali development becomes easy, the dissolution of the exposed portion caused by the developer is suppressed, and the drawing of a fine resist pattern becomes easy. More preferably, it is 45 to 120 mgKOH / g.

[0142] The weight average molecular weight of the carboxyl group-containing resins (A1) and (A2) described above varies depending on the resin skeleton, but is generally preferably 2000 to 150000, more preferably 5000 to 100000, from the viewpoints of moisture resistance (solubility in water), resolution, developability, etc. of the coating film after exposure. In addition, the weight average molecular weight represents a standard polystyrene conversion value measured by gel permeation chromatography (GPC).

[0143] Next, the unsaturated primary acid copolymer type carboxyl group-containing resin (A3) is described. The carboxyl group-containing resin (A3) is obtained by copolymerizing a (meth)acrylic acid ester with a compound having one unsaturated group and at least one carboxyl group in one molecule. Examples of (meth)acrylates include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, and hexyl (meth)acrylate; hydroxyl-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and caprolactone-modified 2-hydroxyethyl (meth)acrylate; and glycol-modified (meth)acrylates such as methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, isooctyloxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate. These may be used alone or in combination of two or more.

[0144] In addition, as compounds having one unsaturated group and at least one carboxyl group in one molecule, there can be cited: acrylic acid, methacrylic acid, modified unsaturated monocarboxylic acid with extended chain between unsaturated group and carboxylic acid, for example, unsaturated monocarboxylic acid having ester bond by (meth) acrylate β-carboxyethyl ester, 2-acryloyloxyethyl succinic acid, 2-acryloyloxyethyl hexahydrophthalic acid, lactone-modified unsaturated monocarboxylic acid, modified unsaturated monocarboxylic acid having ether bond, maleic acid, etc., and compounds containing two or more carboxyl groups in the molecule, etc. These can be used alone or in combination of two or more.

[0145] In the present invention, as the unsaturated primary acid copolymer type carboxyl-containing resin (A3), a resin in which an unsaturated group is introduced into the resin by reacting a part of the acid group of the unsaturated primary acid copolymer resin (i.e., a copolymer resin obtained by copolymerizing a (meth)acrylate and a compound having one unsaturated group and at least one carboxyl group in one molecule) with an epoxy group of an unsaturated compound containing an alicyclic epoxy group. By using the unsaturated primary acid copolymer type carboxyl-containing resin together with the carboxyl-containing resins of (A1) and (A2) in a specific ratio, the PCBT properties are further improved.

[0146] As the unsaturated compound containing alicyclic epoxy group which reacts with a part of the acid group of the above-mentioned unsaturated primary acid copolymer resin, it is preferable that the compound has one free radical polymerizable unsaturated group and alicyclic epoxy group in one molecule, for example, the compound having both alicyclic epoxy group and acryloyl group, for example, can be listed: 3,4-epoxycyclohexyl methacrylate, 3,4-epoxycyclohexyl ethyl acrylate, 3,4-epoxycyclohexyl butyl acrylate, etc. These can be used alone, and two or more kinds can also be used in combination.

[0147] In addition to the compounds having both an alicyclic epoxy group and an acryloyl group, unsaturated compounds containing an aliphatic epoxy group such as glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, and allyl glycidyl ether may be used in combination.

[0148] The weight average molecular weight of the carboxyl group-containing resin (A3) varies depending on the resin skeleton, but is generally preferably 3,000 to 100,000, more preferably 5,000 to 50,000, from the viewpoint of moisture resistance (solubility in water), resolution, developability, etc. of the coating film after exposure.

[0149] In the photosensitive resin composition of the present invention, the total compounding amount of the carboxyl-containing resin of (A1) and the carboxyl-containing resin of (A2) is 60 to 80 mass % relative to the whole carboxyl-containing resin of (A). In addition, the compounding amount of the carboxyl-containing resin of (A3) is 40 to 20 mass % relative to the whole carboxyl-containing resin of (A). By containing these 3 kinds of carboxyl-containing resins in a specific ratio, the characteristics required by the solder resist such as insulation reliability can be met, and the contamination of the plating solution and the poor plating can also be suppressed. In addition, the compounding amount of each carboxyl-containing resin is the compounding amount converted into solid content (the same below).

[0150] The total amount of the carboxyl-containing resin (A1) and the carboxyl-containing resin (A2) is preferably 65 to 75% by mass based on the total amount of the carboxyl-containing resin (A) from the viewpoint of gold plating resistance.

[0151] Regarding the blending ratio of each carboxyl-containing resin (A1) to (A3) above, the blending amount of the carboxyl-containing resin (A1) is preferably contained in a ratio of 10 to 60% by mass, and more preferably in a ratio of 10 to 40% by mass, relative to the entire carboxyl-containing resin (A), from the viewpoint of suppressing non-adhesion of gold plating.

[0152] The amount of the carboxyl group-containing resin (A2) is preferably 20 to 60% by mass, more preferably 40 to 60% by mass, based on the total amount of the carboxyl group-containing resin (A), from the viewpoint of suppressing re-adhesion of development residues to the substrate.

[0153] The amount of the carboxyl group-containing resin (A3) blended is preferably 40 to 20% by mass based on the total amount of the carboxyl group-containing resin (A) from the viewpoint of suppressing PCT resistance and gold plating abnormalities.

[0154] (A) The amount of the carboxyl-containing resin is preferably 20 to 60% by mass relative to the photosensitive resin composition as a whole. By setting it to 20% by mass or more, the coating strength can be improved. In addition, by setting it to 60% by mass or less, the viscosity becomes appropriate and the processability is improved. More preferably, it is 25 to 50% by mass.

[0155] <(B) Photopolymerizable Monomer>

[0156] The (B) photopolymerizable monomer contained in the photosensitive resin composition is a monomer having an ethylenically unsaturated double bond. As the (B) photopolymerizable monomer, the monomers described in the above curable resin composition can be used.

[0157] The amount of the photopolymerizable monomer (B) in the photosensitive resin composition is preferably 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, based on 100 parts by mass of the carboxyl group-containing resin, in terms of solid content.

[0158] <Photopolymerization Initiator>

[0159] The photosensitive resin composition of the present invention may contain a photopolymerization initiator in order to react the (A) carboxyl group-containing resin or the (B) photopolymerizable monomer by exposure. As the photopolymerization initiator, those listed in the curable resin composition may be used.

[0160] The amount of the photopolymerization initiator is preferably 1 to 20 parts by mass relative to 100 parts by mass of the carboxyl group-containing resin (A) in terms of solid content. When the amount is 1 part by mass or more, the photocurability of the photosensitive resin composition is good, and the coating properties such as chemical resistance are also good. In addition, when the amount is 20 parts by mass or less, the effect of reducing exhaust gas can be obtained, and the light absorption on the surface of the cured coating is good, and the deep curability is difficult to reduce. More preferably, it is 2 to 15 parts by mass.

[0161] In the present invention, a photopolymerization initiator and a photoinitiator aid or a sensitizer may be used together. As the photopolymerization initiator aid or the sensitizer, those described in the curable resin composition may be used.

[0162] <(C) Thermosetting component>

[0163] The photosensitive resin composition of the present invention contains (C) a thermosetting component in addition to (A) a carboxyl group-containing resin and (B) a photopolymerizable monomer. By containing a thermosetting component, the barrier properties (e.g., etching resistance, etc.) of the cured film in the subsequent process are improved, and resolution and peelability can be taken into account in a high-dimensional manner. (C) As the thermosetting component, the substance shown as "curable resin" in the above-mentioned curable resin composition can be used.

[0164] In addition, the photosensitive resin composition of the present invention can preferably use an epoxy resin having an isocyanurate ring among epoxy resins from the viewpoint of achieving both resolution and peelability. Examples of epoxy resins having an isocyanurate ring include: bifunctional epoxy isocyanurate compounds including 1,3-bis(2,3-epoxypropyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; 1,3,5-tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; 3,5-Tris(2,3-epoxy-2-methylpropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(3,4-epoxybutyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(4,5-epoxypentyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione ketone; tetrafunctional or higher polyfunctional epoxy isocyanurate compounds such as 1,3,5-tri{2-[2,2-bis(2,3-epoxypropoxymethyl)butoxycarbonyl]ethyl}-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, etc., preferably a substance containing a trifunctional epoxy isocyanurate compound, and particularly preferably a substance containing 1,3 ,5-tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(3,4-epoxybutyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, or 1,3,5-tris(4,5-epoxypentyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.

[0165] Examples of commercially available epoxy resins having an isocyanurate ring include TEPIC-PAS B26L, TEPIC-PAS B22, TEPIC-VL, TEPIC-UC, TEPIC-G, TEPIC-S, TEPIC-SP, and TEPIC-SS manufactured by Nissan Chemical Corporation.

[0166] The amount of the thermosetting component (C) to be compounded is preferably 0.8 to 2.5 mol, more preferably 1.0 to 2.0 mol, of the number of functional groups of the thermosetting component (C) that react per 1.0 mol of the carboxyl group contained in the carboxyl group-containing resin (A).

[0167] In particular, when an epoxy resin is used as the (C) thermosetting component, the epoxy group of the epoxy resin is preferably 1.0 to 2.0 mol per 1.0 mol of the carboxyl group of the (A) carboxyl-containing resin. By setting it to 1 mol or more, the residual carboxyl group in the cured film can be prevented, and good heat resistance, alkali resistance, electrical insulation, etc. can be obtained. In addition, by making the above-mentioned mixing amount less than 2 mol, it is possible to prevent low molecular weight cyclic (sulfide) ether groups from remaining in the dried coating film, thereby ensuring the strength of the cured film.

[0168] <Thermal Curing Catalyst>

[0169] The photosensitive resin composition may contain a thermosetting catalyst for accelerating the curing of the thermosetting component (C). As the thermosetting catalyst, the ones listed in the above curable resin composition can be used.

[0170] The above-mentioned thermosetting catalyst can be used alone or in combination of two or more. From the viewpoint of the storage stability of the photosensitive resin composition and the heat resistance of the cured film, the mixing amount of the thermosetting catalyst is preferably 0.01 to 8 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the carboxyl group-containing resin (A), calculated as solid content.

[0171] <(D) Inorganic filler>

[0172] The photosensitive resin composition of the present invention may be mixed with (D) an inorganic filler as required in order to improve the physical strength of the cured film. As the inorganic filler, known fillers may be used, and in particular, silicon dioxide, talc, mica, aluminum oxide, calcium oxide, magnesium oxide, zinc oxide, calcium carbonate, magnesium carbonate, fly ash, dewatered sludge, kaolin, clay, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, hydrotalcite, aluminum silicate, magnesium silicate, calcium silicate, calcium silicate, wollastonite, potassium titanate, magnesium sulfate, calcium sulfate, magnesium phosphate, sepiolite, boron nitride, aluminum borate, silicon dioxide balloon, glass flake, glass, ironmaking slag, copper, iron, zinc oxide, various magnets, zinc oxide, zinc oxide, zinc oxide, zinc oxide, zinc oxide, zinc oxide, zinc oxide stone and other magnetic powders, cement, glass powder, Neuburg silica, diatomaceous earth, antimony trioxide, magnesium oxide, hydrated aluminum, hydrated gypsum, alum and barium sulfate may be listed. The other inorganic fillers may be used alone or in combination of two or more.

[0173] Among the above substances, silicon dioxide, talc and barium sulfate are preferred. The silicon dioxide may be amorphous or crystalline, or a mixture thereof. Amorphous (fused) silicon dioxide is particularly preferred.

[0174] From the viewpoint of dispersibility, the average particle size (D50) of the inorganic filler used is preferably 0.1 to 100 μm, more preferably 0.1 to 50 μm. In addition, the average particle size refers to the particle size of 50% of the volume accumulation obtained by laser diffraction scattering particle size distribution measurement method. In addition, the average particle size of the filler refers to the value measured as described above for the filler before the photosensitive resin composition is prepared (pre-stirred, kneaded).

[0175] The amount of the inorganic filler in the photosensitive resin composition is preferably 1 to 500 parts by mass, more preferably 10 to 300 parts by mass, based on solid content per 100 parts by mass of the carboxyl group-containing resin. This can further improve the anti-adhesive force reduction property and thermal cycle resistance of the photosensitive resin composition.

[0176] The inorganic filler may be a filler that has been surface treated in order to improve its dispersibility in the photosensitive resin composition. By using an inorganic filler that has been surface treated, aggregation can be suppressed. The surface treatment method is not particularly limited, and any known and commonly used method may be used. It is preferred to treat the surface of the inorganic filler using a surface treatment agent having a curable reactive group, such as a coupling agent having a curable reactive group as an organic group.

[0177] As the coupling agent, the substances shown in the above curable resin composition can be used. These silane coupling agents are preferably fixed on the surface of the inorganic filler in advance by adsorption or reaction. Here, the treatment amount of the coupling agent relative to 100 parts by mass of the inorganic filler is preferably 0.5 to 10 parts by mass.

[0178] <Other ingredients>

[0179] The photosensitive resin composition of the present invention may contain, in addition to the above components, substances described as “other components” in the above curable resin composition as necessary.

[0180] The photosensitive resin composition of the present invention may contain an organic solvent from the viewpoint of ease of preparation and coating properties. As the organic solvent, those described in the curable resin composition can be used.

[0181] The amount of the organic solvent in the photosensitive resin composition can be appropriately changed according to the material constituting the photosensitive resin composition, for example, it can be 30 to 300 parts by mass relative to 100 parts by mass of the (A) carboxyl-containing resin (solid content). The amount of the organic solvent in this amount also includes the organic solvent contained in the varnish when a resin such as the (A) carboxyl-containing resin is used as the varnish.

[0182] The photosensitive resin composition of the present invention may be used in the form of a dry film or in the form of a liquid. When used in the form of a liquid, it may be a one-component or two-component or more liquid.

[0183] <Dry film>

[0184] The curable resin composition and the photosensitive resin composition of the present invention may also be in the form of a dry film, the dry film having a first film and a resin layer formed on the first film, the resin layer being composed of the curable resin composition or the photosensitive resin composition. The first film in the dry film of the present invention refers to a film that is at least bonded to the resin layer when laminated into an integral shape by heating or the like in a manner that contacts the side of the resin layer composed of the curable resin composition or the photosensitive resin composition formed on the dry film on a substrate such as a substrate. The first film may also be peeled off from the resin layer in the process after lamination. In particular, in the present invention, it is preferably peeled off from the resin layer in the process after exposure.

[0185] In order to prepare a dry film, the curable resin composition or the photosensitive resin composition is diluted with an organic solvent to adjust the viscosity to an appropriate level, and is applied to the first film in a uniform thickness using a comma coater, a knife coater, a lip coater, a rod coater, an extrusion coater, a reverse coater, a transfer roll coater, a gravure coater, a spray coater, etc., and is usually dried at a temperature of 50 to 130° C. for 1 to 30 minutes to obtain a film. The coating film thickness is not particularly limited, but is generally selected so that the film thickness after drying is in the range of 1 to 150 μm, preferably 10 to 60 μm.

[0186] As the first film, any known film can be used without particular limitation. For example, a film made of thermoplastic resins such as polyester film such as polyethylene terephthalate or polyethylene naphthalate, polyimide film, polyamide-imide film, polypropylene film, and polystyrene film can be preferably used. Among them, polyester film is preferred from the viewpoints of heat resistance, mechanical strength, and operability. In addition, a laminate of these films can also be used as the first film.

[0187] Furthermore, from the viewpoint of improving mechanical strength, the thermoplastic resin film is preferably a film stretched in a uniaxial direction or a biaxial direction.

[0188] The thickness of the first film is not particularly limited, and may be, for example, 10 μm to 150 μm.

[0189] After forming the resin layer of the curable resin composition or the photosensitive resin composition on the first film, a peelable second film is preferably laminated on the surface of the resin layer for the purpose of preventing dust from adhering to the surface of the resin layer. The second film in the dry film of the present invention refers to a film that is peeled off from the resin layer before lamination when the resin layer side of the dry film is laminated by heating or the like in such a way that the dry film is in contact with a base material such as a substrate to form an integral body.

[0190] As the second film that can be peeled off from the resin layer, for example, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a surface-treated paper, etc. can be used. When peeling the second film, the adhesion between the resin layer and the second film is smaller than the adhesion between the resin layer and the first film.

[0191] The thickness of the second film is not particularly limited, and may be, for example, 10 μm to 150 μm.

[0192] <Method for producing cured product>

[0193] The cured product of the present invention can be obtained by curing the resin layer of the above-mentioned curable resin composition or dry film. For example, the curable resin composition is adjusted to a viscosity suitable for the coating method using the above-mentioned organic solvent, and is applied to the surface of the substrate by dip coating, flow coating, roller coating, rod coating, screen printing, curtain coating, etc., and then the organic solvent contained in the composition is volatilized and dried (temporary drying) at a temperature of 60 to 100° C., thereby forming a non-sticky resin layer. In addition, in the case of a dry film, after the resin layer is attached to the substrate in a manner in contact with the substrate by a laminator, the carrier film is peeled off to form a resin layer on the substrate.

[0194] As the above-mentioned substrate, in addition to printed wiring boards or flexible printed wiring boards in which circuits are pre-formed with copper or the like, materials such as copper-clad laminates for high-frequency circuits such as paper phenol, paper epoxy resin, glass cloth epoxy resin, glass polyimide, glass cloth / stainless steel cloth epoxy resin, glass cloth / paper epoxy resin, synthetic fiber epoxy resin, fluororesin·polyethylene·polyphenylene ether, polyphenylene ether, and cyanate ester are also used. In addition, all grades of copper-clad laminates (FR-4, etc.) can be listed. In addition, metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer plates, etc.

[0195] In the case of a dry film, it is preferably laminated to a substrate under pressure and heating using a vacuum laminator or the like. By using such a vacuum laminator, even if there are irregularities on the surface of the circuit substrate, bubbles will not be mixed in because the dry film is in close contact with the circuit substrate, and the filling property of the recessed part on the surface of the substrate is also improved. The pressurization condition is preferably about 0.1 to 2.0 MPa, and the heating condition is preferably 40 to 120°C.

[0196] When the cured resin composition contains an organic solvent, it is preferred to volatilize and dry after applying the cured resin composition on the surface of the substrate. The volatilization drying can be carried out using a hot air circulation drying furnace, an IR furnace, a hot plate, a convection oven, etc. (a method in which a substance having a heat source of steam-based air heating method is used to make the hot air in the dryer contact with the countercurrent and a method of blowing from a nozzle to the substrate).

[0197] After forming a resin layer on a substrate, it is selectively exposed to active energy rays through a photomask having a predetermined pattern, and the unexposed portion is developed with a dilute alkali aqueous solution (e.g., a 0.3-3 mass % sodium carbonate aqueous solution) to form a pattern of a cured product. In the case of a dry film, after exposure, the first film is peeled off from the dry film and developed, thereby forming a patterned cured product on the substrate. In addition, in the case of a dry film, the first film may be peeled off from the dry film before exposure, and the exposed resin layer may be exposed and developed as long as the properties are not impaired.

[0198] As an exposure machine used in the above-mentioned active energy ray irradiation, any device equipped with a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, etc., which irradiates ultraviolet rays in the range of 350 to 450 nm can be used. In addition, a direct drawing device (for example, a laser direct imaging device that directly draws an image with a laser using CAD data from a computer) can also be used. As a lamp light source or a laser light source of a direct writer, the maximum wavelength can be in the range of 350 to 450 nm. The exposure amount used for image formation varies depending on the film thickness, etc., but is generally 10 to 1000 mJ / cm 2, preferably 20 to 800 mJ / cm 2 within the range.

[0199] As the above-mentioned development method, an immersion method, a shower method, a spray method, a brush method, etc. can be used, and as the developer, an alkaline aqueous solution such as potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, etc. can be used.

[0200] The cured product of the present invention can be obtained by heat curing (e.g., 100 to 220° C.) after the above exposure and development (actual curing). At this time, since the average linear expansion coefficient is in the range of 70 to 100 ppm / ° C., it is preferred to irradiate the cured product with active energy rays after heat curing. By irradiating the cured product with active energy rays again after heat curing, the photopolymerizable monomer and the like are further cured according to the composition of the curable resin composition, and the desired average linear expansion coefficient can be adjusted, and as a result, the adhesiveness of the marking ink after curing is also excellent.

[0201] The active energy ray irradiation after heat curing also depends on the composition of the curable resin composition, but preferably 500 to 2000 mJ / cm 2 As the device, there are: high pressure mercury lamp (80W / cm 3 3 lights) etc.

[0202] The cured product of the present invention is used to form a solder resist, a cover layer, or an interlayer insulating layer of an electronic component such as a printed wiring board. In addition, it can also be used to form a solder dam of a printed wiring board. Among them, it is preferably used to form a solder resist. According to the cured product of the present invention, when a cured product is formed on a printed wiring board described later, it is easy to apply a marking ink on its surface, and the adhesion to the cured marking ink is excellent, and a mark with excellent visibility of text or marks is formed on the surface.

[0203] In addition, regarding the method of forming a cured product from the photosensitive resin composition of the present invention or the resin layer of the dry film thereof, the same method as the method of producing the cured product of the present invention described above can be used.

[0204] In addition, in the cured product obtained from the photosensitive resin composition of the present invention or the resin layer of its dry film, after the pattern of the cured product is formed on the substrate after exposure and development, the cured product is irradiated with active energy rays and then heat-cured (for example, 100 to 220° C.), or irradiated with active energy rays after heat-curing, or finally cured (actually cured) only by heat-curing, it is possible to form a coating (cured coating) composed of a cured product having excellent properties such as adhesion and hardness.

[0205] [Printed wiring board]

[0206] The printed wiring board of the present invention has the cured product of the present invention, or a cured product obtained from the photosensitive resin composition of the present invention or a dry film thereof. The method for producing the cured product is as described above.

[0207] As the substrate for forming the printed wiring board, in addition to the printed wiring board or flexible printed wiring board in which the circuit is pre-formed with copper or the like, materials such as paper phenol, paper epoxy resin, glass cloth epoxy resin, glass polyimide, glass cloth / stainless steel cloth epoxy resin, glass cloth / paper epoxy resin, synthetic fiber epoxy resin, fluororesin·polyethylene·polyphenylene ether, polyphenylene ether, cyanate ester and the like copper-clad laminates for high-frequency circuits are also used. In addition, all grades of copper-clad laminates (FR-4, etc.) can be listed. In addition, metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer plates, etc. are also used.

[0208] In addition, in the printed wiring board of the present invention, as described above, after the cured film is formed on the substrate, components such as electronic components are mounted on the substrate by solder reflow treatment. The solder reflow treatment can be performed by a conventionally known method. In addition, the solder reflow is usually performed under treatment conditions such as 245 to 260° C. for 5 to 10 seconds.

[0209] The photosensitive resin composition of the present invention or its dry film is suitable for use in the manufacture of electronic components such as printed wiring boards, and is more preferably used to form a permanent coating. In this case, the photosensitive resin composition of the present invention or its dry film is used to form a cured product by the above method or the like. In the case where the resin layer of the photosensitive resin composition of the present invention or its dry film is insulating, it is preferably used to form a solder resist, a cover film, or an interlayer insulating layer. In addition, the photosensitive resin composition of the present invention can also be used to form a solder dam.

[0210] [Example]

[0211] Next, the present invention will be described in more detail by giving examples, but the present invention is not limited to these examples. In addition, the following "parts" and "%" are all based on mass unless otherwise specified.

[0212] <Synthesis Example 1 (Synthesis of Carboxyl Group-Containing Resin Varnish A1-1)>

[0213] 220 parts of o-cresol novolac epoxy resin (manufactured by DIC Corporation, EPICLON N-695, epoxy equivalent: 214, average number of functional groups: 7.6) were placed in a four-necked flask equipped with a stirrer and a reflux cooler, and 214 parts of carbitol acetate were added and heated to dissolve. Next, 0.1 parts of hydroquinone as a polymerization inhibitor and 2.0 parts of dimethylbenzylamine as a reaction catalyst were added. The mixture was heated to 95-105°C, 72 parts of acrylic acid were slowly added dropwise, and the reaction was carried out for 16 hours. The reaction product was cooled to 80-90°C, 106 parts of tetrahydrophthalic anhydride were added, the reaction was carried out for 8 hours, and the reaction was taken out after cooling. The solid content of the carboxyl resin solution thus obtained was 65%, the acid value of the solid was 85 mgKOH / g, and the weight average molecular weight was 10,000. Hereinafter, the resin solution is referred to as varnish A1-1.

[0214] <Synthesis Example 2 (Synthesis of Carboxyl-containing Resin A1-2)>

[0215] In a flask equipped with a thermometer, a stirrer, a dropping funnel and a reflux cooler, add 200 parts of a phenol novolac type epoxy resin (P-201 manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent = 200) and 96.4 parts of carbitol acetate as a solvent, and heat to dissolve. Next, add 0.1 parts of hydroquinone as an inhibitor and 2.0 parts of triphenylphosphine as a reaction catalyst. Heat the mixture to 95-105°C, slowly drop 72 parts of acrylic acid, and react for about 16 hours until the acid value is 3.0 mgKOH / g or less. After cooling the reaction product to 80-90°C, add 76.1 parts of tetrahydrophthalic anhydride, and analyze by infrared absorption spectroscopy. React for about 6 hours until the absorption peak of the anhydride (1780cm -1 ) disappeared. 96.4 parts of Idemitsu Petrochemical Co., Ltd. aromatic solvent Ipsol #150 was added to the reaction solution, diluted and taken out. The carboxyl resin solution thus obtained had a solid content of 65%, an acid value of 78 mgKOH / g, and a weight average molecular weight of 8000. Hereinafter, the resin solution is referred to as varnish A1-2.

[0216] <Synthesis Example 3 (Synthesis of Carboxyl Group-Containing Resin Varnish A2-1)>

[0217] After dissolving 371 parts of bisphenol A epoxy resin (epoxy equivalent 650 g / eq, softening point 81.1°C) having an average degree of polymerization n of 3.3 and 925 parts of epichlorohydrin in 462.5 parts of dimethyl sulfoxide, 52.8 parts of 98.5% sodium hydroxide were added at 70°C for 100 minutes. After the addition, the mixture was further reacted at 70°C for 3 hours. After the reaction was completed, 250 parts of water were added for washing. After oil-water separation, most of the dimethyl sulfoxide and excess unreacted epichlorohydrin were recovered from the oil layer by distillation under reduced pressure, and the reaction product containing the residual by-product salt and dimethyl sulfoxide was dissolved in 750 parts of methyl isobutyl ketone, and 10 parts of 30% sodium hydroxide were added, and the mixture was reacted at 70°C for 1 hour. After the reaction was completed, the mixture was washed twice with 200 parts of water. After oil-water separation, methyl isobutyl ketone was distilled and recovered from the oil layer to obtain an epoxy resin with an epoxy equivalent of 287 g / eq and a softening point of 64.2° C. According to the epoxy equivalent, about 3.1 of the 3.3 alcoholic hydroxyl groups in the above-mentioned starting material bisphenol A type epoxy resin were epoxidized.

[0218] 310 parts of the obtained epoxy resin and 282 parts of carbitol acetate are added to a flask, heated, stirred, and dissolved to 90°C. The obtained solution is temporarily cooled to 60°C, 72 parts (1 mole) of acrylic acid, 0.5 parts of methylhydroquinone, and 2 parts of triphenylphosphine are added, heated to 100°C, and reacted for about 60 hours to obtain a reactant with an acid value of 0.2 mgKOH / g. 140 parts (0.92 moles) of tetrahydrophthalic anhydride are added thereto, heated to 90°C, and a carboxyl-containing resin solution is obtained. The solid content of the carboxyl-containing resin solution obtained in this way is 64.0%, the acid value of the solid content is 100 mgKOH / g, and the weight-average molecular weight is 15,000. Hereinafter, this resin solution is referred to as varnish A2-1.

[0219] <Synthesis Example 4 (Synthesis of Carboxyl Group-Containing Resin Varnish A2-2)>

[0220] After dissolving 380 parts of bisphenol F type epoxy resin (epoxy equivalent 950 g / eq, softening point 85°C) having an average degree of polymerization n of 6.2 and 925 parts of epichlorohydrin in 462.5 parts of dimethyl sulfoxide, 60.9 parts (1.5 mol) of 98.5% sodium hydroxide were added at 70°C for 100 minutes. After the addition, the mixture was further reacted at 70°C for 3 hours. After the reaction was completed, 250 parts of water were added for washing. After oil-water separation, most of the dimethyl sulfoxide and excess unreacted epichlorohydrin were recovered from the oil layer by distillation under reduced pressure, and the reaction product containing the residual by-product salt and dimethyl sulfoxide was dissolved in 750 parts of methyl isobutyl ketone, and 10 parts of 30% sodium hydroxide were added, and the mixture was reacted at 70°C for 1 hour. After the reaction was completed, the mixture was washed twice with 200 parts of water. After oil-water separation, methyl isobutyl ketone was distilled and recovered from the oil layer to obtain an epoxy resin with an epoxy equivalent of 310 g / eq and a softening point of 69° C. According to the epoxy equivalent, about 5 of the 6.2 alcoholic hydroxyl groups in the above-mentioned starting material bisphenol F type epoxy resin were epoxidized.

[0221] 310 parts of the obtained epoxy resin and 282 parts of carbitol acetate are added to a flask, heated and stirred to 90°C to dissolve. The obtained solution is temporarily cooled to 60°C, 72 parts (1 mole) of acrylic acid, 0.5 parts of methylhydroquinone, and 2 parts of triphenylphosphine are added, heated to 100°C, and reacted for about 60 hours to obtain a reactant with an acid value of 0.2 mgKOH / g. 140 parts (0.92 moles) of tetrahydrophthalic anhydride are added thereto, heated to 90°C, and a carboxyl-containing resin solution is obtained. The solid content of the carboxyl-containing resin solution thus obtained is 65.0%, the acid value of the solid content is 100 mgKOH / g, and the weight-average molecular weight is 15,000. Hereinafter, this resin solution is referred to as varnish A2-2.

[0222] <Synthesis Example 5 (Synthesis of Carboxyl Group-Containing Resin Varnish A3-1)>

[0223] 900 parts of diethylene glycol dimethyl ether as a solvent were placed in a stirrer, a thermometer, a reflux cooler, a dropping funnel, and a 2-liter separable flask equipped with a nitrogen inlet tube, and heated to 90° C. After heating, 309.9 parts of methacrylic acid, 116.4 parts of methyl methacrylate, and 109.8 parts of lactone-modified 2-hydroxyethyl methacrylate (made by Di-unit Co., Ltd., Plastic FM1) were added dropwise thereto over 3 hours, and 21.4 parts of bis(4-tert-butylcyclohexyl) peroxydicarbonate (made by NOF Corporation, Palmitoyl TCP) as a polymerization initiator were added dropwise, and then aged for 6 hours to obtain a product. In addition, the reaction was carried out under a nitrogen atmosphere.

[0224] Next, 363.9 parts of 3,4-epoxycyclohexylmethyl acrylate (CYCLOMER A200 manufactured by Daicel Corporation), 3.6 parts of dimethylbenzylamine as a ring-opening catalyst, and 1.80 parts of hydroquinone monomethyl ether as a polymerization inhibitor were added to the obtained product, and the mixture was heated to 100° C. and stirred to perform an epoxy ring-opening addition polymerization reaction. After 16 hours, a carboxyl-containing resin having a solid content of 53.8%, an acid value of the solid content of 108.9 mgKOH / g, and a weight average molecular weight of 25,000 was obtained. Hereinafter, this resin solution is referred to as varnish A3-1.

[0225] <Synthesis Example 6 (Synthesis of Carboxyl-containing Resin A3-2)>

[0226] In a four-necked flask equipped with a reflux cooler, a thermometer, a glass tube for nitrogen replacement, and a stirrer, 42 parts of methacrylic acid, 43 parts of methyl methacrylate, 35 parts of styrene, 100 parts of carbitol acetate, 0.5 parts of dodecyl mercaptan, and 4 parts of azobisisobutyronitrile were added, and heated at 75° C. for 5 hours under a nitrogen stream to allow polymerization reaction to proceed, thereby obtaining a carboxyl-containing resin solution having a solid content of 50%, an acid value of the solid content of 120 mgKOH / g, and a weight average molecular weight of 25000. Hereinafter, this resin solution is referred to as varnish A3-2.

[0227] <Synthesis Example 7 (Synthesis of Carboxyl Group-Containing Resin Varnish B1)>

[0228] In an autoclave equipped with a thermometer, a nitrogen gas introduction device and an oxyalkylene introduction device, and a stirring device, 119.4 parts of a novolac type cresol resin (CRG951, an industrial phenolic resin manufactured by AICA Industries, Ltd., OH equivalent: 119.4), 1.19 parts of potassium hydroxide, and 119.4 parts of toluene were added, and the nitrogen gas in the system was replaced while stirring, and the temperature was raised by heating. Then, 63.8 parts of propylene oxide was slowly added dropwise, and the mixture was stirred at 125 to 132°C and 0 to 4.8 kg / cm 2 The mixture was allowed to react for 16 hours. Then, the mixture was cooled to room temperature, and 1.56 parts of 89% phosphoric acid was added and mixed to the reaction solution to neutralize potassium hydroxide, thereby obtaining a propylene oxide reaction solution of a novolac type cresol resin having a solid content of 62.1% and a hydroxyl value of 182.2 g / eq. This is a material in which an average of 1.08 mol of alkylene oxide is added per 1 equivalent of phenolic hydroxyl groups.

[0229] Next, 293.0 parts of the obtained oxyalkylene reaction solution of the novolac type cresol resin, 43.2 parts of acrylic acid, 11.53 g of methanesulfonic acid, 0.18 parts of methyl hydroquinone and 252.9 parts of toluene were added to a reactor equipped with a stirrer, a thermometer and an air blowing tube, and air was blown in at a rate of 10 ml / min, and the mixture was reacted at 110°C for 12 hours while stirring. 12.6 parts of water generated by the reaction were distilled off as an azeotropic mixture with toluene. Then, the reaction solution was cooled to room temperature, neutralized with 35.35 parts of a 15% sodium hydroxide aqueous solution, and then washed with water. Then, toluene was distilled off with an evaporator while being substituted with 118.1 parts of carbitol acetate to obtain a novolac type acrylate resin solution.

[0230] Next, 332.5 parts of the obtained novolac type acrylate resin solution and 1.22 parts of triphenylphosphine were added to a reactor equipped with a stirrer, a thermometer and an air blowing tube, and air was blown in at a rate of 10 ml / min. While stirring, 60.8 parts of tetrahydrophthalic anhydride were gradually added, and the mixture was reacted at 95-101° C. for 6 hours. In this way, a resin solution of a carboxyl group-containing photosensitive resin having a solid content of 71%, an acid value of the solid content of 88 mgKOH / g, and a weight average molecular weight of 2500 was obtained. Hereinafter, this resin solution is referred to as varnish B1.

[0231] <Synthesis Example 8 (Synthesis of Carboxyl-containing Resin Varnish B2)>

[0232] 220 parts of cresol novolac epoxy resin (manufactured by Nippon Kayaku Co., Ltd., EOCN-104S, softening point 92°C, epoxy equivalent 220) and 40.2 parts of dimethylol propionic acid were placed in a flask equipped with a stirring device, a cooling tube and a thermometer, and 260 parts of carbitol acetate were added and heated to dissolve at 90°C. Then, the resin solution was cooled to 60°C, 0.7 parts of triphenylphosphine was added, and the mixture was heated to 100°C and reacted for about 32 hours to obtain a resin solution with a solid content of 50% and an epoxy equivalent of 371 g / equivalent.

[0233] Next, 203 parts of 1,5-dihydroxynaphthalene with a hydroxyl equivalent of 80 g / equivalent and 1097 parts of EPICLON-840 (manufactured by DIC Corporation, epoxy equivalent of 180) of bisphenol A type epoxy resin were added to a reaction vessel equipped with a gas introduction pipe, a stirring device, a cooling pipe, a thermometer and a dropping funnel for continuous dropping of an alkali metal hydroxide aqueous solution, and dissolved at 120°C under stirring in a nitrogen atmosphere. Then, 0.65 parts of triphenylphosphine were added, and the temperature in the flask was raised to 150°C and kept at 150°C, and the reaction was carried out for about 90 minutes to obtain an epoxy compound with an epoxy equivalent of 365 g / equivalent. Then, the temperature in the flask was cooled to 70°C or less, 2058 parts of epichlorohydrin and 1690 parts of dimethyl sulfoxide were added, and the temperature was raised to 70°C and kept under stirring. Then, 244 parts of 48% sodium hydroxide were continuously dropped over 90 minutes, and the reaction was further carried out for 3 hours. After the reaction, most of the excess epichlorohydrin and dimethyl sulfoxide were recovered by vacuum distillation, and the reaction product containing by-product salts and dimethyl sulfoxide was dissolved in methyl isobutyl ketone and washed with water. After the organic solvent layer and the water layer were separated, the methyl isobutyl ketone was removed by vacuum distillation from the organic solvent layer to obtain a polynuclear epoxy compound with an epoxy equivalent of 275 g / equivalent (the epoxidation rate of the alcohol-soluble hydroxyl group was about 48%).

[0234] Next, 371 parts of the resin solution prepared as described above and 137.5 parts of the multinuclear epoxy compound were placed in a flask equipped with a stirring device, a cooling tube and a thermometer, 137 parts of carbitol acetate were added, heated to dissolve, 0.46 parts of methylhydroquinone and 1.38 parts of triphenylphosphine were added, heated to 95-105°C, 72 parts of acrylic acid were gradually added dropwise, and the reaction was allowed to proceed for 16 hours. The reaction product was cooled to 80-90°C, 146 parts of tetrahydrophthalic anhydride were added, and the reaction was allowed to proceed for 8 hours. The reaction was subjected to oxidation and total oxidation determination of the reaction solution by potentiometric titration, and the obtained addition rate was used for tracking, with the reaction rate of 95% or more being the end point. In this way, a resin solution of a carboxyl-containing resin having a solid content of 62%, an acid value of the solid content of 102 mgKOH / g, and a weight average molecular weight of 10,000 was obtained. Hereinafter, the resin solution is referred to as varnish B2.

[0235] <Synthesis Example 9 (Synthesis of Carboxyl Group-Containing Resin Varnish B3)>

[0236] 1070 parts of hydroxyphenol novolac epoxy resin (Epiclon N-695 manufactured by DIC Corporation, softening point 95°C, epoxy equivalent 214, average functional group number 7.6), 360 parts of acrylic acid and 1.5 parts of hydroquinone were added to 650 parts of carbitol acetate, heated and stirred to 100°C, and uniformly dissolved. Then, 4.3 parts of triphenylphosphine were added, heated to 110°C and reacted for 2 hours, and then 1.6 parts of triphenylphosphine were added, and the temperature was raised to 120°C and reacted for another 12 hours.

[0237] 525 parts of aromatic hydrocarbon (T-SOL150 manufactured by Standard Oil Co., Ltd. Osaka Sales Co., Ltd.) and 608 parts (4.0 mol) of tetrahydrophthalic anhydride were added to the obtained reaction solution, and the mixture was reacted at 110°C for 4 hours. Furthermore, 142.0 g of glycidyl methacrylate was added to the obtained reaction solution, and the mixture was reacted at 115°C for 4 hours. Thus, a resin solution of a carboxyl-containing resin having a solid content of 65%, an acid value of the solid content of 77 mgKOH / g, and a weight average molecular weight of 11000 to 12000 was obtained. Hereinafter, the resin solution is referred to as varnish B3.

[0238] <Preparation of Curable Resin Composition>

[0239] The components described in Table 1 below were mixed and mixed at room temperature using a three-roll mill to obtain the curable resin compositions described in the table. In addition, each numerical value in the table represents a mass part. In addition, the mixing amount (numerical value) of each component represents the mixing amount of the solid component (the organic solvent (methyl acetate) described in the table is the actual mixing amount).

[0240] In addition, each component *1 to *19 in the following Table 1 is as follows.

[0241] *1: Dipentaerythritol penta- and hexaacrylate, photopolymerizable monomer (DPHA, manufactured by Kyoei Chemical Co., Ltd.)

[0242] *2: Urethane acrylate, oligomer (CN9178, manufactured by Arkema (Sartomer))

[0243] *3: Cresol novolac type epoxy resin (RN-695, manufactured by DIC Corporation)

[0244] *4: Triepoxy resin having an isocyanurate ring (TEPIC-S, manufactured by Nissan Chemical Co., Ltd.)

[0245] *5: Bisphenol A epoxy resin (jER828, manufactured by Mitsubishi Chemical Corporation)

[0246] *6: Dicyclopentadiene skeleton-containing multifunctional solid epoxy resin (HP-7200, manufactured by DIC Corporation)

[0247] *7: Biphenyl aralkyl type epoxy resin (YX-4000, manufactured by Nippon Kayaku Co., Ltd.)

[0248] *8: Biphenyl aralkyl type epoxy resin (NC3000H, manufactured by Mitsubishi Chemical Corporation)

[0249] *9: α-Aminoacetophenone-based photopolymerization initiator (Omnirad 907, manufactured by Agenmon Resins Co., Ltd.)

[0250] *10: Acylphosphine oxide-based photopolymerization initiator (Omnirad 819, manufactured by Agenmon Resins Co., Ltd.)

[0251] *11: α-Aminoacetophenone-based photopolymerization initiator (Omnirad 369, manufactured by Agenmon Resins Co., Ltd.)

[0252] *12: Titanocene-based photopolymerization initiator (JMT-784, manufactured by Yueyang Jinmaotai Technology Co., Ltd.)

[0253] *13: Amorphous silica (FS-3DC, manufactured by Denka Co., Ltd., D50 = 2.9 μm)

[0254] *14: Amorphous silica (HS-311, manufactured by Nippon Steel Chemical Materials Co., Ltd., D50 = 2.2 μm)

[0255] *15: Talc (LMP-100, manufactured by Fuji Talc Industry Co., Ltd.)

[0256] *16: Barium sulfate (B-100, manufactured by Sakai Chemical Industry Co., Ltd.)

[0257] *17: 2,4-Diethylthioxanthone (KAYACURE DETX-S, manufactured by Nippon Kayaku Co., Ltd.)

[0258] *18: 2-isopropylthioxanthone (KAYACURE ITX, manufactured by Nippon Kayaku Co., Ltd.)

[0259] *19: Melamine (manufactured by Nissan Chemical Co., Ltd., D50 = 0.5 μm)

[0260] <Production of Cured Material>

[0261] The curable resin compositions of Examples and Comparative Examples were solid-printed on copper-clad laminates for printed wiring boards (FR-4, thickness 1.6 mm, size 150×95 mm) by screen printing so that the dry coating film had a thickness of 20 μm, and dried at 80° C. for 30 minutes to form coating films.

[0262] Next, the coating film was exposed to a pattern that was completely left on the coating film, and developed at 30°C with a 1wt% Na2CO3 solution for 60 seconds. As the exposure amount, after drying, exposure was performed using an exposure device equipped with a metal halide lamp via a step exposure meter (Kodak No. 2), and the optimal exposure amount was when the pattern of the step exposure meter remaining when developing (30°C, 0.2MPa, 30°C, 1wt% Na2CO3 solution) was 7 segments. Furthermore, after exposure and development, the coating film was cured at 150°C for 30 minutes. After curing, for Examples 1, 2, and Comparative Example 2, exposure was further performed using a high-pressure mercury lamp (80W / cm 3 3 lamps 1000mJ / cm 2 ) is irradiated on the coating surface to obtain a test substrate 1 on which a cured product (cured film) is formed.

[0263] <Evaluation of Physical Properties of Cured Product>

[0264] The average linear expansion coefficient and glass transition temperature (Tg) of the obtained cured product at 0 to 180° C. were measured as follows.

[0265] The cured product obtained as described above was cut into a test piece with a width of 3 mm and a length of 30 mm, and a thermal mechanical analyzer (TMA / SS6000, manufactured by Seiko Instruments Co., Ltd.) was used to measure the thermal expansion coefficient in the tensile mode. The maximum load for the stretching was 50 N / m, the span (distance between chucks) was 10 mm, and the heating rate was 10°C / min. The test piece was mounted on a thermal mechanical analyzer, heated from 30°C to 200°C, left for 10 minutes, cooled to -30°C at a cooling rate of -10°C / min, and measured at a heating rate of 10°C / min from -30°C to 250°C, and the measured values ​​at 0°C and 180°C were read, and the average linear expansion coefficient (α) was calculated by the following formula.

[0266] α=(1 / LS)×[{L(180)-L(0)} / (T(180)-T(0)]

[0267] (In addition,

[0268] LS: Length of the test piece (cured product) before measurement (measured value)

[0269] L(0): Change in length of the test piece (cured product) at 0°C (measured value)

[0270] L(180): Change in length of the test piece (cured product) at 180°C (measured value)

[0271] T(0): 0(℃)

[0272] T(180): 180(℃).

[0273] In addition, a straight line A passing through two points of 0°C and 30°C and a straight line B passing through two points of 150°C and 180°C were drawn from the obtained TMA curve, and the temperature of the point where the straight line A and the straight line B intersected (extrapolated point) was taken as the Tg of the cured product of the present invention.

[0274] The measurement results are shown in Table 1 below.

[0275]

Table 1

[0276]

[0277]

[0278] <Mark evaluation>

[0279] (1) Printability

[0280] On the surface of the cured coating film of the test substrate obtained as described above, a marking ink (PMR-6000W30, manufactured by Taiyo Ink Manufacturing Co., Ltd.) was printed in a rectangular shape of 10×20 mm to a film thickness of 20 μm after curing. This was dried at 80° C. for 30 minutes to form a marking object. The printed state of the marked portion was confirmed with the naked eye, and the marking printability was evaluated according to the following evaluation criteria.

[0281] ○: No bleeding or blurring is seen

[0282] ×: Bleeding or blurring can be seen

[0283] The evaluation results are shown in Table 2 below.

[0284] (2) Adhesion

[0285] On the surface of the cured coating film of the test substrate obtained as described above, a marking ink (PMR-6000W30, manufactured by Taiyo Ink Manufacturing Co., Ltd.) was used to print a rectangular shape of 10×20 mm, and the cured film thickness was 20 μm. After drying at 80°C for 30 minutes, the printed part was exposed to a pattern of text / marks with a remaining thickness of about 10 to 20 μm, and it was developed at 30°C with 1wt% Na2CO3 for 60 seconds. As the exposure amount, after drying, an exposure device equipped with a metal halide lamp was used to expose through a step exposure meter (Kodak No. 2), and the pattern of the step exposure meter remaining when developing for 60 seconds (30°C, 0.2MPa, 30°C, 1wt% Na2CO3 solution) was 8 stages, which was the optimal exposure amount. Furthermore, the developed coating film was washed with 10°C water for 60 seconds, and cured at 180°C for 45 minutes to form a marking object.

[0286] Next, an adhesive tape was attached to the marked portion and a peel test was performed. The evaluation criteria were as follows.

[0287] ◎: No shedding

[0288] ○: Slight peeling was observed in part

[0289] ×: Complete peeling confirmed

[0290] The evaluation results are shown in Table 2 below.

[0291] (3) Marking visibility

[0292] The evaluation samples subjected to the above-mentioned (2) adhesiveness evaluation were visually checked to see whether the characters and symbols on the marked portion were recognizable. The evaluation criteria for the visibility of the mark were as follows.

[0293] ◎: All characters and marks can be recognized

[0294] ○: Some characters or symbols are difficult to read

[0295] ×: It is difficult to recognize characters and symbols overall.

[0296] The evaluation results are shown in Table 2 below.

[0297]

Table 2

[0298]

[0299] As can be seen from Table 1, in the cured product (Examples 1 to 3) whose average linear expansion coefficient is in the range of 70 to 100 ppm / °C when the temperature changes from 0°C to 180°C, the printability of the marking ink is good, and a mark can be formed which has excellent adhesion to the marking ink and excellent visibility of text and symbols.

[0300] In contrast, when the average linear expansion coefficient is less than 70 ppm / °C or exceeds 100 ppm / °C (Comparative Examples 2 and 3), the printability of the marking ink is poor and the adhesion to the marking ink is insufficient.

[0301] In addition, it can be seen that even if the average linear expansion coefficient when the temperature changes from 0°C to 180°C is in the range of 70 to 100 ppm / °C, the cured product formed using the curable resin composition that does not contain amorphous silica has poor printing properties with the marking ink and insufficient adhesion to the marking ink, just like the other comparative examples.

[0302] <Preparation of Photosensitive Resin Composition>

[0303] The components described in Table 3 below were mixed and mixed using a three-roll mill at room temperature to obtain the photosensitive resin compositions described in the table. In addition, each numerical value in the table represents a mass part. In addition, the blending amount of each carboxyl group-containing resin in the table represents the blending amount in the varnish obtained as described above. In addition, each component *1 to *19 in Table 3 below is as described above.

[0304] <Evaluation of Photosensitive Resin Composition>

[0305] (1) Evaluation of reattachment of development residue

[0306] This evaluation was performed as an item for evaluating the suppression of electroplating defects. Specifically, each photosensitive resin composition obtained as described above was formed into a coating film by double-sided screen printing in a manner such that the film thickness after development was 20 μm on a substrate having a comb-shaped L / S=100 μm / 100 μm pattern of a 0.5 m×0.5 m×1.6 mm pad portion polished by buffing.

[0307] Next, the substrate formed with the coating film was kept for 10 minutes and then dried in a hot air circulation drying oven at 80°C for 40 minutes. After the substrate after the coating film was dried was placed at room temperature for 30 minutes, 100 sheets were developed using a developer (manufactured by Tokyo Chemical Industry Co., Ltd., solder resist developer (150L tank)) in which a 1% Na2CO3 aqueous solution (liquid temperature 30°C) was placed, and the number of reattached developing residues was confirmed with the naked eye. The evaluation criteria are as follows.

[0308] ○: 0 attached again

[0309] △: 1 to 9 pieces attached again

[0310] ×: Attach 10 or more

[0311] The evaluation results are shown in Table 3 below.

[0312] (2) PCBT (Pressure Cooker Bias Test)

[0313] Specifically, each photosensitive resin composition was formed into a coating film by double-sided screen printing on a substrate having a comb-shaped L / S=100 μm / 100 μm pattern of a pad portion so that the film thickness after development was 20 μm.

[0314] Next, the substrate with the coating film formed was dried in a hot air circulation drying oven at 80°C for 40 minutes. The substrate after the coating film was dried was left at room temperature for 30 minutes and then heated at 400 mJ / cm 2The film was exposed to an exposure amount of 1000 nm, and developed for 60 seconds using a developer (manufactured by Tokyo Chemical Industry Co., Ltd., solder resist developer (150L tank)) containing a 1% Na2CO3 aqueous solution (liquid temperature 30°C). Then, a post-curing treatment was performed at 150°C for 60 minutes to cure the coating film, and a substrate with a cured film (hereinafter referred to as a "test substrate") was prepared.

[0315] The insulation reliability of the test substrate was measured in the tank using an insulation degradation evaluation tester (MIG-8600B manufactured by IMV Corporation) at 121°C and 97% humidity with an applied voltage of 30V. The measured resistance value decreased to 10 6 The time it takes to lose insulation is Ω or less. The evaluation criteria are as follows.

[0316] ◎: More than 150 hours

[0317] ○: 100 to 149 hours

[0318] △: 50~99 hours

[0319] ×: Less than 49 hours

[0320] The evaluation results are shown in Table 3 below.

[0321] (3) Plating evaluation

[0322] Specifically, the test substrate was immersed in a 30°C acidic degreasing solution (20 vol% aqueous solution of Metex L-5B manufactured by MacDermid Corporation) for 3 minutes for degreasing, and then immersed in running water for 3 minutes for washing.

[0323] Next, the test substrate was immersed in a 14.3 wt % ammonium persulfate aqueous solution at room temperature for 3 minutes for soft etching, and then immersed in running water for 3 minutes for water washing. The test substrate was immersed in a 10 vol % sulfuric acid aqueous solution at room temperature for 1 minute, and then immersed in running water for 30 seconds to 1 minute for water washing.

[0324] Next, the test substrate was immersed in a catalyst solution (10 vol% aqueous solution of Melplate Activator 350 manufactured by Melplate Corporation) at 30° C. for 7 minutes to provide the catalyst, and then immersed in running water for 3 minutes to wash.

[0325] The catalyst-applied test substrate was immersed in a nickel plating solution (Melplate Ni-865M, a 20 vol% aqueous solution, pH 4.6, manufactured by Melplate Co., Ltd.) at 85°C for 30 minutes to perform electroless nickel plating. The test substrate was immersed in a 10 vol% sulfuric acid aqueous solution at room temperature for 1 minute, and then immersed in running water for 30 seconds to 1 minute for water washing.

[0326] Next, the test substrate was immersed in a 95°C gold plating solution (manufactured by Meiluda Co., Ltd., an aqueous solution of Aurolectroless UP 15 vol% and potassium gold cyanide 3 vol%, pH 6) for 30 minutes to perform electroless gold plating to a thickness of Ni 5 μm and Au 0.05 μm, then immersed in running water for 3 minutes for water washing, and then immersed in 60°C warm water for 3 minutes for water washing. After sufficient water washing, the water was fully drained and dried to obtain a test substrate plated with electroless gold.

[0327] The pad portion of the test substrate subjected to the electroless gold plating as described above was visually confirmed to determine whether plating had been performed, and the presence or absence of unplated pads was evaluated based on the following criteria.

[0328] ○: No unplated area found

[0329] △: One spot without plating was observed

[0330] ×: Many unplated areas were observed

[0331] The evaluation results are shown in Table 3 below.

[0332] In addition, the following evaluation was performed as an evaluation item for suppressing plating solution contamination: Specifically, the pad portion of the test substrate was visually checked for abnormalities on the plated surface, and the evaluation for abnormalities on the plated surface was performed based on the following criteria.

[0333] ○: No abnormal parts

[0334] △: There is 1 abnormal part

[0335] ×: There are multiple abnormal areas

[0336] The evaluation results are shown in Table 3 below.

[0337]

Table 3

[0338]

[0339]

[0340] As shown in Table 3, the photosensitive resin compositions (Examples 4 to 8) in which three specific carboxyl group-containing resins are combined in a specific ratio can satisfy the properties required of solder resists such as insulation reliability, while also suppressing contamination of the plating solution and occurrence of plating defects.

[0341] On the other hand, in the photosensitive resin composition using only the carboxyl-containing resin having a novolac skeleton as the carboxyl-containing resin (Comparative Example 4), although contamination of the plating solution and occurrence of plating defects can be suppressed, the properties required for the solder resist, such as insulation reliability, are insufficient.

[0342] In addition, as the carboxyl-containing resin, it can be considered that in the photosensitive resin composition (Comparative Example 5) in which a carboxyl-containing resin having a novolac skeleton and a carboxyl-containing resin having a bisphenol skeleton are used together, or in the photosensitive resin composition (Comparative Example 6) in which a carboxyl-containing resin having a bisphenol skeleton and an unsaturated primary acid copolymer-type carboxyl-containing resin are used together, abnormalities occur on the plating surface and contamination of the plating solution occurs.

[0343] In the photosensitive resin composition (Comparative Example 7) using two types of carboxyl-containing resins, a carboxyl-containing resin having a novolac skeleton and an unsaturated primary acid copolymer type carboxyl-containing resin as carboxyl-containing resins, defects such as non-plating occurred due to the influence of residues in the developer.

[0344] Furthermore, it can be seen that, as a carboxyl-containing resin, even when three specific types are combined, the photosensitive resin composition (Comparative Example 8) in which the components are outside the prescribed proportion range satisfies the properties required by the solder resist such as insulation reliability, but due to the influence of the residue in the developer, it causes defects such as non-plating, and abnormalities occur on the plated surface, resulting in contamination of the plating solution.

Claims

1. A cured product, which is a cured product composed of a curable resin composition, wherein the curable resin composition comprises a curable resin and an inorganic filler, characterized in that: The inorganic filler comprises amorphous silicon dioxide, The average linear expansion coefficient of the cured product when the temperature changes from 0° C. to 180° C. is 70 to 100 ppm / ° C.

2. The cured product according to claim 1, wherein The glass transition temperature (Tg) is in the range of 100 to 120°C.

3. The cured product according to claim 1, wherein The average linear expansion coefficient of the cured product when the temperature changes from 0° C. to 180° C. is 70 to 85 ppm / ° C.

4. The cured product according to claim 1, wherein The curable resin includes a thermosetting resin and a photocurable resin.

5. The cured product according to claim 1, wherein The amorphous silica is contained in an amount of 2 to 30% by mass based on the total mass of the curable resin composition in terms of solid content.

6. A photosensitive resin composition comprising (A) a carboxyl group-containing resin, (B) a photopolymerizable monomer, and (C) a thermosetting component, characterized in that: (A) The carboxyl group-containing resin comprises: (A1) a carboxyl-containing resin having a novolac skeleton; (A2) a carboxyl group-containing resin having a bisphenol skeleton; and (A3) unsaturated acid copolymer type carboxyl group-containing resin, The total amount of the carboxyl-containing resin (A1) and the carboxyl-containing resin (A2) is 60 to 80% by mass based on the total amount of the carboxyl-containing resin (A). The amount of the carboxyl group-containing resin (A3) blended is 40 to 20% by mass based on the total amount of the carboxyl group-containing resin (A).

7. The photosensitive resin composition according to claim 6, wherein The carboxyl-containing resin (A3) is a reaction product of an unsaturated primary acid copolymer resin and an unsaturated compound containing an alicyclic epoxy group.

8. The photosensitive resin composition according to claim 6, wherein The amount of the carboxyl group-containing resin (A1) blended is 10 to 60% by mass based on the total amount of the carboxyl group-containing resin (A).

9. The photosensitive resin composition according to claim 6, wherein The amount of the carboxyl group-containing resin (A1) blended is 20 to 50% by mass based on the total amount of the carboxyl group-containing resin (A).

10. The photosensitive resin composition according to claim 6, wherein The (C) thermosetting component includes an epoxy resin having an isocyanurate ring.

11. The photosensitive resin composition according to claim 6, wherein It also contains (D) an inorganic filler.

12. The photosensitive resin composition according to claim 11, wherein The (D) inorganic filler comprises fused silica.

13. A dry film, wherein: A photosensitive resin composition according to claim 6 is applied to a first film and dried to form a resin layer.

14. A solidified product, wherein The photosensitive resin composition according to claim 6 or the resin layer of the dry film according to claim 13 is cured.

15. The cured product according to claim 1 or 14, wherein Used for solder resist.

16. A printed wiring board, wherein: The cured product according to claim 1 or 14 is provided on a substrate.

Citation Information

Patent Citations

  • Alkali-developable solder resist composition

    JP1998142793A

  • Oxime ester compound and photopolymerization initiator containing the same

    JP2004359639A

  • Dimer oxime ester compound and photopolymerization initiator comprising the same compound as active ingredient

    JP2005097141A

  • Oxime ester compound having thiophene structure and photopolymerization initiator containing the compound

    JP2005220097A

  • Oxime ester compound and photopolymerization initiator containing the compound

    JP2006160634A